Interconnected macroporous foamed hydrogels enable stable and efficient nitrogen removal in low temperature Anammox systems - Wanqi Liu; Ning An; Yuhan Zhu; Peng Gao; Tingting Liu; Xingrong Yao; Kaiyao Hu; Jun Li; Dongyue Li; Zhaoming Zheng; Zehao Zhang (Water Research, 2027)

A dynamic RNA editing landscape in porcine spleen highlights a post-transcriptional mechanism for immune maturation - Ling Zeng; Yiyang Li; Juan Liu; Chenxi Liu; Ning Gao; Jun He; Yuebo Zhang (Molecular Genetics and Genomics, 2026)

Integrative multi-omics analysis and machine learning identify M2 macrophage–induced ferroptosis resistance in glioblastoma - Fangzhou Guo; Teng Deng; Jun Yan; Yong Mo; Qianrong Huang; Qian Jiang; Ligen Mo; Shipeng Ning; Chao Li (Functional & Integrative Genomics, 2026)

Full-field strain-informed characterization of post-cracking toughening response in locally SFRC-enhanced PCCP - Bin Zheng; Zhongwen Shi; Ning Li; Jun Li; Wenming Pan; Jiyuan Yin; Ningyuan Xu (Tunnelling and Underground Space Technology, 2026)

Exogenous melatonin partially alleviates the effects of reduced nitrogen by enhancing photosynthetic carbon assimilation, nitrogen assimilation, and grain yield in field-grown rice - Yangming Ma; Xiana Tie; Yuanqing Shi; Ning Liu; Ruhongji Liu; Leilei Li; Guanzhou Luo; Ruijie Li; Cheng Wang; Xinghai Huang; Zhonglin Wang; Zongkui Chen; et al. (Field Crops Research, 2026)

Sperm cryopreservation of Sebastes schlegelii and application in large scale seed breeding production - XiaoYang Guo; Yichao Zhang; JinWei Huang; Teng Guo; XueYing Wang; ShiHong Xu; Ning Zhao; Zongzhu Liu; Jun Li; QingHua Liu (Theriogenology, 2026)

Decoding glomalin: Mycorrhizal hyphae-secreted glomalin-related soil protein in a zero-carbon background unveils Hsp60 homology and functional molecular architecture - Xiao-Qing Liu; Ci Deng; Li-Jun Zhou; Ying-Ning Zou; Qiang-Sheng Wu (Soil Biology and Biochemistry, 2026)

PpPRE1 and PpPRE2 mediate gibberellin-induced internode elongation by regulating brassinosteroid biosynthesis in peach - Huanbing Lu; Mengmeng Zhang; Ning Liu; Bo Zhao; Jun Cheng; Bin Tan; Xianbo Zheng; Wei Wang; Xia Ye; Haipeng Zhang; Xiaobei Wang; Zhiqian Li; et al. (Plant Science, 2026)

Comparative analysis of composition, volatile compounds, and bioactivities in pomace skins and seeds from different wine grape varieties prior to and following fermentation - Juan-Juan Zhu; Jia-Ning Yan; Xiao-Fang Li; Hao-Hao Zhao; Wen-Qi Wang; Hai-Jun Ma (Food Chemistry, 2026)

Dual-mechanism chloride capture in capacitive deionization enabled by Cu-TADV-COF/LDH/CC heterostructures - Wei Ji; Zhiquan Chen; Yuanyuan Ning; Chunyan Li; Jun Yang; Minjie Shi; Chao Yan (Chemical Engineering Journal, 2026)

Effects of the hydration state of psyllium husk on the gel properties of pork meat batters under 50% phosphate reduction: Protein molecular interactions and lipid conformational alterations - Yu Wang; Hao Chen; Ning-ning Liu; Ke Li; Bo Chen; Jun-guang Li; Yan-hong Bai (Meat Science, 2026)

Low-frequency deficit irrigation in a semi-arid vineyard of Xinjiang's Manas region: Effects on grape and wine aroma composition across three vintages - Ning Shi; Meng-Bo Tian; Hao-Cheng Lu; Yi-Fan Zhao; Ming-Yu Li; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Zhen-Zhen Zhang; Keji Yu; Yi-Bin Lan; Fei He; et al. (Food Research International, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

Synergistic regulation of bimetallic d-band centers in NiM-NiMOx (M = Co/Cu) catalysts toward enhancing selective hydrogenation - Liangmin Ning; Jun Xie; Shiyan Sheng; Jiawen Wang; Tianyu Zhang; Shuai Li; Shuanglu Fu; Tianqi Xie; Jiaoyang Wang; Wei Chen; Meng Gao; Kunhua Wang; et al. (Chemical Engineering Journal, 2026)

Structural characterization of a pectic polysaccharide from Bombax ceiba L. flowers and its neuroprotective effects via the microbiota–gut–brain axis - Ziyi Zhang; Boya Zhang; Wenchen Yu; Qiushuang Jia; Ruijiao Zhu; Mengcong Li; Jun Li; Yazhi Wang; Lu Yu; Ziwei Song; Ning Gu; Chenfeng Ji (Carbohydrate Polymers, 2026)

Concentration-dependent variation in carbon allocation and microbial assembly in chain elongation microbiota: Comparative effects of acetate, ethanol, and lactate - Ya-Ning Song; Li-Juan Chai; Ling Ao; Jun-Lan Mei; Yu-Long Li; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Bioresource Technology, 2026)

Integrating agricultural management and factor interaction effects for interpretable maize yield prediction in the U.S. Corn Belt - Liang Li; Ning Lu; Mengmeng Hong; Ying Sun; Jiaxu Wang; Jun Qin (Agricultural and Forest Meteorology, 2026)

Double-layered soil profile structure in an agro-pastoral ecotone revealed by geochemical characteristics: implications for wind erosion in northern North China - Jian-Yu Liu; Chun-Lei Zha; Zhi-Qiang Yin; Ling Peng; Kai-Ning Lv; Jun Li; Guo-Li Yuan (Environmental Monitoring and Assessment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Extended state observer based adaptive heading control for unmanned surface vehicles with event-triggered mechanism and input quantization - Guanpeng Xu; Jun Ning; Xin Hu; Tieshan Li; Wei Li (Ocean Engineering, 2026)

Finite-time unmanned surface vehicles heading control based on event-triggering with neural network disturbance observer and input quantizer - Zhihui Li; Shuyang Xie; Jun Ning; Xin Hu; Kai Wang (Ocean Engineering, 2026)

Nonlinear dynamics and optimal deployment of a deep-ocean mining riser with surface-mounted flow-disturbing robots - Shanfei Fan; Xiaoqiang Guo; Kelun Yang; Reza N. Jazar; Edson Denis Leonel; Nerguibaatar Tsend; Xianbin Liu; Yuwen Wang; Liming Dai; Jun Liu; Ning Zong; He Chen; et al. (Ocean Engineering, 2026)

Hydrate extraction riser gas-liquid-solid three-phase coupled flow simulation experiment: flow characteristics and prediction of flow pattern transition boundaries - Xiaoqiang Guo; Qi Gao; Yuechao Liu; Guanlong Jia; Ying Li; Jun Liu; Liming Dai; Ning Zong (Ocean Engineering, 2026)

Microclimate-adjusted carbon density modeling improves carbon density estimation for photovoltaic-impacted grasslands in Inner Mongolia - Jiaxu Wang; Ning Lu; Ying Sun; Liang Li; Jun Qin (Journal of Environmental Management, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Three-dimensional multi-layer LDH/CS/PPy composites for efficient chloride ion removal - Chunyan Li; Yuanyuan Ning; Wei Ji; Miejie Shi; Jun Yang; Chao Yan (Chemical Engineering Journal, 2026)

Buffer-free BOZn coordination sites enable efficient Fe(VI) oxidation for organic pollutant removal - Xin-Jia Chen; Yu-Kun Huang; Ning Li; Pi-Jun Duan; Chang-Wei Bai; Zhi-Quan Zhang; Jing Wang; Ying Shao; Xiao-Wei Xu; Jin-Song Guo; Fei Chen (Chemical Engineering Journal, 2026)

Deletion of electron-bifurcating [FeFe]-hydrogenase enhances H2-driven CO2 fixation and ethanol production in Clostridium ljungdahlii - Zhi-Qiong Wen; Yu-Zhen Li; Hai-Jia Su; Jun-Zhe Zhang; Zi-Yong Liu; Shu-Ning Wang; Hui Wang; Fu-Li Li; Xiao-Qing Ma (Bioresource Technology, 2026)

A genetic clash of sister groups: first-ever intergeneric and interspecific mitogenome comparisons between two close gall midge genera (Cecidomyiidae: Cecidomyiinae: Cecidomyiini): the floral and veggie-versatile Contarinia and the mango-mad Procontarinia, with phylogenetic applications - Xiu-Fang Dong; Yi-Fan Zhang; Xu-Yuan Gao; Ning-Bo Ma; Yu Ji; Yan-Fei Li; Yi-Ran Mu; Zheng-Hao Yue; De-Wei Wei; Yong-Hao Yu; Hai-Li Qiao; Wen-Jun Bu; et al. (Arthropod-Plant Interactions, 2026)

Expression of Transforming Growth Factor Beta 1 in Lung Adenocarcinoma and Its Relationship with Circulating Tumour Cells - Ning Chen; Duo-Jun Qiu; Jian-Zhu Yang; Gui-Yun Zhu; Li-Fei Kang; Xiao-Ying An; Zhi-Ming Xu; Xiao-Xia Li (Biochemical Genetics, 2026)

Monomeric and dimeric sesquiterpenoids from Artemisia princeps Pamp and their anti-inflammatory activity - Hong-Xia Li; Si-Yu Bai; Bao-Jun Su; Dong Liang; Ning Li; Gui-Jie Zhang (Phytochemistry, 2026)

Ultraviolet-ozone tuned organic-inorganic interface for high-performance PbS quantum dot short-wave infrared photodetectors - Jun Han; Ning Feng; Chuan Wei; Li Yan; Chengrun Shu; Jiatong Liu; Zhouying Wu; Hao Yan; Meili Xu; Yaowu He; Xiaomin Xu; Hong Meng (Chemical Engineering Journal, 2026)

Modulating Ti-O-Bi-based charge transport channels across Bi6O7/Ti3C2Tx interface for augmented targeted iodide ion removal via capacitive deionization - Nan Feng; Xinping Fu; Mingxing Liang; Yuting Ning; Chenghao Li; Tongtao Fan; Huan Zhang; Wei Yao; Donghai Yuan; Jun Cui (Chemical Engineering Journal, 2026)

Shear performance of prefabricated utility tunnel joints considering the effect of connectors - Chao Zhang; Jiao-jiao Chen; Wei-ning Zhong; Xin Li; Chen-chen Sun; You-jun Xu; Xin Han; Jun-yi Gao; Jian-jun Wang; Zhi-qiang Fu (Tunnelling and Underground Space Technology, 2026)

Phase-modulated engineering of oxygen-doped molybdenum disulfide for boosting visible light-driven photocatalytic tetracycline degradation - Ze Yuan; Chenghao Li; Nan Feng; Xinping Fu; Yuting Ning; Wei Yao; Lepu Ci; Jun Cui (Journal of Environmental Chemical Engineering, 2026)

A strategy for in situ sustainable PET degradation in soil by genetically engineered bacteria constructed from indigenous strains - Ya-jun Lai; Tian-yu Wan; Zi-ye Zhou; Ge Lyu; Jia-ning Wang; Kun Liu; Yue-zhong Li; Li Zhuo (Journal of Hazardous Materials, 2026)

Nanostructured electrospun nitrocellulose: Stabilization mechanisms and degradation kinetics of organic stabilizers - Wen-Jie Xu; Xue-Ning Cheng; Zhong-Xuan Han; Zhan-Jun Yang; Shu-Na Zhao; Hao Liu; Mi Li; Lin Jiang (Fuel, 2026)

β-Cyclodextrin-Magnetic Sodium Alginate Composite-Modified Biochar Immobilizes Chlorpyrifos in Soil: Reducing Its Mobility - Yufu Xie; Dexin Shan; Xinyue Zhang; Jun Li; Jingyuan Ning; Guangli Yi; Huimin Chen; Tingfen Xiang (Water, Air, & Soil Pollution, 2026)

Mobile Observations of Intracity Variations in Atmospheric CO2 and CH4 - Jun Wang; Wei Xiao; Ning Hu; Ruonan Li; Honghui Xu; Yibo Liu; Lingbing Bu; Longlong Chen; Yuanze Liu; Xuhui Lee (Advances in Atmospheric Sciences, 2026)

New nor-tirucallane triterpenoid with antitumor activity from Ailanthus altissima (mill.) swingle - Can Liu; Jun-ling Guo; Shuo-yu Zhao; Ning-ning Shi; Yu-cheng Gu; Chun-hui Liang; Man-li Zhang (Natural Product Research, 2026)

Three phloridzin derivatives capable of anti-oxidant from Malus toringoides (Rehd) Hughes - Li Liu; Wei-wei Tian; Ying-chao Wang; Can Ren; Dong-mei Yu; Jian-bo Wang; Jun-ning Zhao; Hua Hua (Natural Product Research, 2026)

Prediction of safe water areas under adverse weather conditions for pilot boarding and disembarkation based on PCA and sparse broad learning neural networks - Lizhen Zhu; Wei Li; Jun Ning; Tong Zhang (Ocean Engineering, 2026)

Predatory performances and adaptive strategies of Eocanthecona furcellata (Hemiptera: Pentatomidae) to the larvae of Phauda flammans (Lepidoptera: Phaudidae) - Jian-Zhong Ning; Da-Xing Lu; Xiong Zhao He; Xiao-Yun Wang; Kai Lin; Jun Li; Xia-Lin Zheng (Applied Animal Behaviour Science, 2026)

Dynamic light exposure from afternoon shading reveals aromatic plasticity in grapes and wines from a semi-arid region - Meng-Bo Tian; Ning Shi; Hao-Cheng Lu; Ming-Yu Li; Jia-Yan Wei; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Fei He; Yi-Bin Lan; Chang-Qing Duan; Keji Yu; et al. (Food Chemistry, 2026)

Potential folate-depleting effect of organochlorine pesticide exposure in elevating homocysteine levels - Tian Tian; Ning Kang; Dezheng Fu; Linlin Wang; Lei Jin; Zhiwen Li; Jun Zhang; Jie Qiao; Aiguo Ren; Shengju Yin (Environmental Pollution, 2026)

Promoting the ionic conductivity and self-healing ability of micro-Si anode via a versatile crosslinker of Al(H2PO4)3 - Yang-Ning You; Shu-Hao Guo; Tao Li; Yu-Jun Bai; Xi-Cheng Ma (Chemical Engineering Journal, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Genomic safety assessment and metabolic modulation by Enterococcus faecium 140,623, a probiotic strain from lactasin tablets: implications for obesity management - Yongqi Gan; Cheng Liu; Xiaorui Zheng; Jun Nong; Lanyan Fan; Peng Xie; Yang Li; Bin Zhu; Ling Ning; Zan Zhang (World Journal of Microbiology and Biotechnology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Stable Pacific deep circulation punctuated by episodic intensification during the Mid-Pleistocene Transition - Ke Li; Jun Tian; Ning Zhao; Jianghui Du; Zhonghui Liu; Jinlong Du; Enqing Huang (Global and Planetary Change, 2026)

Dual functions of pyrite modified polyethylene carrier in Anammox biofilm: Promoting biofilm growth and enhancing nitrogen removal - Tingting Liu; Dongyue Li; Peng Gao; Yuhan Zhu; Linzhu Du; Xingrong Yao; Wanqi Liu; Kailun Yang; Xingxing Xiong; Ning An; Jiarui Li; Qian Zhao; et al. (Chemical Engineering Journal, 2026)

Mountain-plain solenoid over a deep basin modified by the Tibetan Plateau terrain effects on synoptic circulations - Zhen Lu; Jun Hu; Tianliang Zhao; Yuqing Zhang; Guicai Ning; Qingjian Yang; Xiaoyun Sun; Zhikuan Li; Deyang Wang (Atmospheric Research, 2026)

Multi-parameter GNSS monitoring for expansive soil hazards: a case study from coastal Texas - Xiongchuan Chen; Shuangcheng Zhang; Yong Fang; Qingtao Zhang; Lidu Zhao; Peng An; Ning Liu; Qi Liu; Ningkang An; Jun Li; Zhilei Ye (Advances in Space Research, 2026)

Probiotics reshape microbial community assembly and functional stability in mud crab (Scylla paramamosain) larvae under high-temperature stress - Junqi Yu; Tong Li; Gengshen Wang; Jun Ling; Wei Wang; Xueyang Wang; Chunyan Yin; Ning Qiao; Chen Chen (Frontiers in Marine Science, 2026)
High-temperature stress threatens sustainable mud crab ( Scylla paramamosain ) aquaculture by destabilizing the larval microbiome and elevating mortality. This study investigates whether probiotic supplementation can modulate microbial community dynamics and functional assembly to enhance heat resilience. Mud crab larvae across four developmental stages (Zoea I to IV, Z1-Z4) were divided into three groups: a probiotic group (supplemented with Lactobacillus , LAC), an antibiotic group (ANT), and a control group (CK). The microbial community was analyzed by 16S rRNA gene sequencing. We then calculated α- and β-diversity indices, constructed co-occurrence networks, and inferred functional profiles using PICRUSt2 to assess the structural and functional responses to the treatments. The larval microbiome exhibited stage-specific structural shifts. Although the LAC group showed a significant reduction in α-diversity at the Z4 stage, it demonstrated higher temporal stability in community structure compared to the CK and ANT groups. Co-occurrence network analysis revealed that LAC simplified inter-taxa relationships by lowering modularity and increasing negative interactions, whereas ANT formed a more modular but less connected network. Deterministic processes dominated the functional assembly. The microbiota in the LAC group was significantly associated with enhanced carbohydrate and amino acid metabolism, while the ANT group up-regulated pathways related to stress response and antibiotic resistance. Our results demonstrate that probiotic Lactobacillus can remodel the microbial ecology of mud crab larvae under thermal stress, promoting a functionally stable and resilient microbiome. These findings provide a mechanistic foundation for employing probiotics to develop temperature-resilient aquaculture practices for S. paramamosain .

Correlation Analysis of Gut Microbiota of Fish in Yi’an Reservoir with Water Quality Parameters and Aquatic Environment Microbiota - Jun Wang; Tienan Li; Pengpeng Qiu; Ning Zhang; Weiwei Guo; Shuang Liu; Tingyu Li; Ji Chen (Fishes, 2026)
Yi’an Reservoir is located on a major tributary of the Baoquan River and hosts abundant aquatic resources, with Cyprinus carpio, Carassius auratus, and Hemiculter leucisculus as the dominant fish species. Water quality parameters significantly shape fish gut microbiota, which in turn plays a crucial role in host physiological functions. This study aimed to characterize the water quality parameters in Yi’an Reservoir and identify the microbial communities in both the aquatic environment and fish guts (C. carpio, C. auratus, and H. leucisculus) through 16S ribosomal RNA sequencing. The objective was to examine the associations of water quality parameters and aquatic environmental microbiota with the assembly of gut microbial communities in fish inhabiting this reservoir system. The water quality parameters showed significant site-specific differences, of which temperature and dissolved oxygen were highest at Location B, while pH was highest at Location A. The Cyanobium_PCC-6307 was identified as a major differentially abundant taxon at the genera level across different sampling sites. Furthermore, the gut microbiota of the same fish species exhibited substantial variation across different sampling sites. Redundancy analysis identified distinct environmental drivers at each location. Specifically, pH, conductivity, and total dissolved solids (TDS) showed positive correlations with the gut microbiota at Location A. In contrast, temperature, dissolved oxygen (DO), and the environmental abundance of Cyanobium PCC-6307 were positively correlated with the gut microbiota at Locations B and C. This study provides important insights for the conservation and management of aquatic resources in reservoir ecosystems.

Design, synthesis and activity evaluation of usnic acid monoesterification derivatives - Qing Zhang; Jun-Li He; Xiao-Xia Zhuo; Yi-Meng Hao; Hong-Ting Duan; Yan Jia; Jing-Jing Wang; Li-Ning Wang (Natural Product Research, 2026)

Analysis of nitrogen removal performance of gel-immobilized cold-acclimated Anammox granules under low temperature and high nitrogen loading rate (NLR) conditions - Linhua Zhang; Jing Zhang; Jun Li; Peng Gao; Jianwei Chen; Dongyue Li; Xingxing Xiong; Sairui Guan; Ning An; Kailun Yang; Tingting Liu; Xingrong Yao; et al. (Process Safety and Environmental Protection, 2026)

Activating silicic gangue tailings via high-Ca/Si ratio all-solid-waste cementitious materials: constructing low-carbon, high-performance cemented backfill and mechanisms - Kexin Li; Jun Yao; Xiangmei Li; Shuqin Li; Ning Min; Zehai Li; Xilin Li (Minerals Engineering, 2026)

Phylogenomic framework, biogeography and character evolution of the genus Campylotropis (Fabaceae, Papilionoideae) - Li-Sha Jiang; Yu Feng; Jun-Yi Zhang; Xiong Li; Min Liao; Heng-Ning Deng; Qi Yu; Bo Xu (Molecular Phylogenetics and Evolution, 2026)

Bioamines-sensitive, antioxidant, and sustainable gelatin-based jelly ice cubes doped with carbon dots for simultaneous preservation and monitoring of seafood freshness - Jun Li; Yanli Li; Feng Cao; Linchen Yin; Yimiao Zhang; Houqi Ning; Zhouyu Wang; Xiaoqi Yu (Food Research International, 2026)

Span80 induced orderly diffusion of monomer for the construction of small pore volume polyamide nanofiltration membrane with high Li/Mg separation ratio - Lu Gao; Yue Miao; Xiaowen Huo; Yingying Zhao; Zhaojing Jing; Xiuling Liu; Haitao Wang; Ning Fan; Qiuying Jia; Kai Ren; Jun Li; Na Chang (Desalination, 2026)

Event-triggered adaptive heading control for unmanned surface vehicles with input quantification and disturbance observer - Zhihui Li; Shuyang Xie; Jun Ning; Xin Hu; Kai Wang (Ocean Engineering, 2025)

Regulating electronegativity difference and piezoelectric strain of the Mo-S-Mo structure via introducing S vacancies for boosting piezo-photoelectric activity - Yanjiao Li; Yuting Ning; Xinping Fu; Yu Jiang; Lianfeng Wang; Jun Cui (Journal of Environmental Chemical Engineering, 2025)

Proteomic insights into DEM-induced oxidative stress: Glycolytic and antioxidant synergy in beef colour stability - Cai-Yun Li; Wen-Jun Zhao; Ya-Ning Qu; Yu-Bin Zhang (Food Chemistry, 2025)

Preservative effects of chlorogenic acid on myofibrillar proteins in golden pomfret: Integrating artificial neural network and molecular simulation - Ning Yang; Shitong Wen; Zizhe An; Jun Yang; Longteng Zhang; Qian Li; Chuan Li; Lulu Zhu (Food Chemistry, 2025)

Cellular indexing of transcriptomes and epitopes by sequencing unveils coordinated RNA and protein landscape in ovary at single-cell resolution - Yujuan Qi; Yuxuan Feng; Xiaoyan Liu; Jiaxin Li; Qiuru Huang; Zhenbei Li; Sen Zheng; Ning Chen; Jie Cheng; Xinhui Yang; Wei Tao; Xiangnan Cao; et al. (Chemical Engineering Journal, 2025)

Correction: Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Characteristics and distribution patterns of volcanic fractures in the Chaganhua Subsag of the Songliao Basin, China - Ning Li; Xuan-long Shan; Jian Yi; Zhong-bo Li; Kai-fang Cao; Jun Tian; Yun-qian Shi; Qing-lei Leng (Applied Geophysics, 2025)

Contarinia maculipennis, a worldwide invasive flower and vegetable pest possessing the particularities of rearrangement and tRNA secondary structures of mitogenome: A potential key to revealing its extensive host radiation - Ning-Bo Ma; Xiu-Fang Dong; Yu Ji; Xin Jin; De-Wei Wei; Yan-Fei Li; Zheng-Hao Yue; Wen-Jun Bu; Ke-Long Jiao (Zoologischer Anzeiger, 2025)

Emerging contaminants in the lower Yangtze River basin: spatiotemporal distribution, ecological risks in surface water, and fate in wastewater treatment plants - Yechao Tian; Yuewei Tang; Hui Wang; Xu Huang; Jun Li; Xun Chen; Ning Zhou; Wentao Li; Aimin Li (Environmental Pollution, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Smart dual-channel fluorescent sensor overcoming cross-interference: Visual detection of Cu(II) and doxycycline in multiple scenarios, and precise discrimination of tetracycline analogs - Yingqi Yuan; Liuqing Fu; Lina Zhang; Jun Xu; Ning Bi; Yongxin Li; Lei Jia (Chemical Engineering Journal, 2025)

Tectonic thickening in stagnant to mobile lid transition facilitated the stabilization of Archean cratons - Ning Ding; Chris Hawkesworth; Xiao-Lei Wang; Rong-Feng Ge; Axel Hofmann; Jun-Yong Li (Chemical Geology, 2025)

Central neuropeptides as key modulators of astrocyte function in neurodegenerative and neuropsychiatric disorders - Meng-jie Yang; Min Jia; Meng Cai; Xiao Feng; Li-ning Huang; Jian-jun Yang (Psychopharmacology, 2025)

Preparation of N263-OA impregnated resin and its study in adsorptive separation of precious metals from wastewater - Shi-lei Lang; Yong-hui Song; Ning Yin; Xin-wei Zhang; Ze-yu Wang; Jia-jun Shi; Yi-xin Wang; Xiao-ming Li (Journal of Environmental Chemical Engineering, 2025)

A bifunctional sensing platform integrated with gel beads-based sensor for ultrasensitive and point-of-care testing of tetracycline and Hg(II) - Xia Zhang; Lina Zhang; Jun Xu; Yingqi Yuan; Yongxin Li; Ning Bi; Lei Jia (Journal of Environmental Chemical Engineering, 2025)

Hydrophilic PVDF membrane doped with Ti3C2 for piezocatalytic purification of water flow - Ning Chen; Jun Han; Xingchen He; Junhui Shao; Najun Li; Dongyun Chen; Jianmei Lu (Journal of Environmental Chemical Engineering, 2025)

Flavoromics analysis and sensory evaluation of wines produced from nine red grape cultivars in Manas region, Xinjiang, China: Implications for terroir adaptation - Ning Shi; Yi-Fan Zhao; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Jia-Yi Deng; Jia-Yan Wei; Ai-Sai Chen; Chi-Fang Cheng; Shu-De Li; Fei He; Keji Yu; et al. (Food Chemistry, 2025)

Highly efficient and sustainable bioconversion of cottonseed meal to high-value products through solid-state fermentation by protease-enhanced Streptomyces sp. SCUT-3 - Zhen-Jie Dai; Ming-Shu Zhang; Zhi-Wei Li; De-Lin Lu; Lei Wu; Can Qin; Hai-Ning Wang; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

An alternative GC–MS library for methylation analysis of polysaccharides via partially methylated aldononitrile acetates - Ye Li; Jia-Ning Gao; Jun Liang; Xin-Hua Zhu; Hai-Xue Kuang; Yong-Gang Xia (Carbohydrate Polymers, 2025)

The effects of pond purification system on intestinal function of channel catfish (Ictalurus punctatus): a focus on intestinal development, digestion and absorption, and junction integrity - Zhong-Bing Zheng; Yu Yang; Jun Liu; Ming-Cheng Zhou; Ju-Hua Li; Long-Jiang Tang; Hai-Long Nie; Kang-Sheng Chen; Feng Liu; Xiang-Ning He; Zhi-Yuan Lu (Frontiers in Marine Science, 2025)
Pond purification system (PPS) is an outdoor aquaculture system designed based on recirculating aquaculture system (RAS) principles, utilizing recirculating water technology, which can achieve large-scale fish farming in the recirculating water system. The purpose of this experiment is to investigate the alterations in growth performance, intestinal histology, digestion-absorption function, and structural integrity of channel catfish raised in PPS. The findings indicated a significant optimization in water quality indicators pertinent to aquaculture, including total nitrogen, total phosphorus, chemical oxygen demand (COD), ammonia nitrogen, nitrite, and dissolved oxygen. Additionally, the growth performance of channel catfish reared in the PPS group was markedly improved. The intestinal morphology of these channel catfish exhibited increased villus height and a reduced number of mucus cells. Furthermore, serum levels of diamine oxidase and D-lactic acid were significantly decreased in channel catfish raised in the PPS group, while the expression of genes related to the apical junction complex was significantly upregulated, suggesting improved intestinal structural integrity. Moreover, the activities of digestive and absorptive enzymes, such as trypsin, amylase, lipase, and Na + -K + -ATPase, were elevated, indicating enhanced digestive and absorptive functions. In conclusion, based on the conditions of this experiment, the pond purification system module used in this study can effectively improve the quality of the aquaculture water, enhance fish growth performance and improve their intestinal health.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Scaling of urban residential building stock system and carbon emissions accounting for vacant houses in China - Wanru Leng; Guangxin Liu; Xiaoyu Cheng; Yang Li; Shoujuan Tang; Jun Ning; Yuanhang Li; Hang Fu; Lei Shi (Resources, Conservation and Recycling, 2025)

Stiffness matters: Exploiting mechanotransduction to guide cellular behavior and potentiate cancer therapy - Jie Wang; Lin Long; Cheng Sun; Ping Li; Sheng Yao; Ning Wang; Jun Xiao (Chemical Engineering Journal, 2025)

Unlocking bio-H2 production potential from straw–sludge co-substrates: The role of Fe/Mn-biochar in alleviating carbon catabolite repression - Ji-wen Wu; Shi-jie You; Chun-shuang Zhou; Qi Xi; Jia-ning Fan; Jun Ma; Guang-li Cao (Chemical Engineering Journal, 2025)

Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Physiological and transcriptomic responses of fall armyworm, Spodoptera frugiperda to host-plant switching - Jun Peng; Renwen Zheng; Jinyuan Zhao; Jinhui Zhang; Qianqian Li; Dongyan Huang; Xin Zhou; Lijuan Liu; Zhuocong Li; Xiaoman Ning; Sihan Lu; Qingfeng Tang (Journal of Pest Science, 2025)

Enhancing the anti-inflammatory efficacy of polysaccharides through processing techniques: a case study on Atractylodes macrocephala - Hong-Da Xuan; Sheng-Nan Shen; Chun-Jin Fu; Jie Zhou; Rui-Xing Chen; Jun-Zhe Zhang; Xiao-Xia Liu; Feng-Qin Li; Yi-Fan Zhao; Dong Zhang; Hai-Ning Lyu; Fang Wang (Natural Product Research, 2025)

Multi-element isotope fractionation analysis to investigate the photosensitized reactions of humic substance with 3-chloroaniline - Ning Min; Jun Yao; Hao Li; Steffen Kümmel; Thomas Schaefer; Hartmut Herrmann; Hans Herrmann Richnow (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Remarkable performance and physical origins of a multi-site functional material for 131I-ion exchange in nuclear medical wastewater - Jiale Liu; Yang-Yang Zhang; Ning Pan; Shiyuan Feng; Guohui Yang; Guohao Zhang; Qiuhong Zhu; Xiaoan Li; Jun-Jie Song; Jun Li; Xiaoqin Nie (Science Bulletin, 2025)

Annual growth bands in the late Carboniferous reef-building colonial rugose coral Ivanovia and their environmental significance - Yong-Li Zhang; Wen-Tao Huang; En-Pu Gong; Guan-Ming Lai; Mark A. Wilson; Jun-Jie Wang; Ning-Feng Du; De-Peng Li (Palaeoworld, 2025)

Effect of rootstocks on growth potential, soil properties and rhizosphere microbiome of Vitis vinifera L. cv. Cabernet Sauvignon - Ning Shi; Xiao Han; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Fei He; Chang-Qing Duan; Ke-Ji Yu; Jun Wang (Plant and Soil, 2025)

SIRT1 Attenuates Neuropathic Pain via CDK5-Kalirin-7 Signaling Pathway in Type 2 Diabetic Rats - Cishan Xie; Yannan Cao; Yujing Shen; Shishu Wu; Junwu Wang; Xiuying Ye; Ning Wei; Hong Cao; Jun Li (Molecular Neurobiology, 2025)

Biodegradation of short-chain phthalate esters (PAEs) by Sinomonas sp. S2 isolated from a soil contaminated by metal(loid)s smelting - Pengfei Shao; Jun Yao; Miaomiao Li; Ning Min (Biodegradation, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Neuroprotective lindenane sesquiterpenoids from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Shan-Rong Luo; Qian-Qing Liu; Rui-Si Tang; Ning-Yu Chen; Di Luo; Lu Guo; Jia Li; Rui Wu; Zha-Jun Zhan (Phytochemistry, 2025)

Assessing how the partial substitution of phosphate by modified chickpea protein affects the technofunctional, rheological, and structural characteristics of pork meat emulsions - Yu Wang; Ning-ning Liu; Ke Li; Bo Chen; Jia-le Wang; Jun-guang Li; Yan-hong Bai (Meat Science, 2025)

Development of a novel chemosensor for photodynamic antimicrobial and fluorescence-colorimetric dual-mode sensing in food preservation and spoilage process monitoring - Nan Wang; Hua-Feng Mao; Lu Wang; Yi-Miao Zhang; Jun Li; Hou-Qi Ning; Shan Qian; Xiang-Gui Chen; Xiao-Qi Yu (Food Chemistry, 2025)

Corrigendum to “How do contributions of organizations impact data inequality in OpenStreetMap?” [Computers, Environment and Urban Systems, Volume 109 (2024), 102077] - Anran Yang; Hongchao Fan; Qingren Jia; Mengyu Ma; Zhinong Zhong; Jun Li; Ning Jing (Computers, Environment and Urban Systems, 2025)

Ratiometric fluorescent nanoprobes based on lanthanide coordination polymers for visual intelligent detection of phosphate - Yongxin Li; Rongrong Zhou; Fei Xue; Ning Bi; Lina Zhang; Qianyang Li; Kai Shi; Jiang Wu; Lei Jia; Jun Xu (Chemical Engineering Journal, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Hydrological changes in the East Asian monsoon region around 4.2 ka precisely reconstructed from multi-proxy stalagmites - Chao-Jun Chen; Yao Wu; Jun-Yun Li; Hai-Wei Zhang; Hai Cheng; Chuan-Chou Shen; You-Feng Ning; Dao-Xian Yuan; R. Lawrence Edwards; Jian Zhang; Ting-Yong Li (Quaternary Science Reviews, 2025)

Event-triggered anti-disturbance trajectory tracking for under-actuated surface vehicle under multiple constraints and input quantization - Yuanning Yue; Jun Ning; Xin Hu; Wei Li (Ocean Engineering, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Time series comparative genomics analysis reveals the adaptive evolution of caproic acid-producing bacteria to the long-term liquor brewing environment - Gan-Lin Li; Jun-Lan Mei; Li-Juan Chai; Xiao-Zhong Zhong; Ya-Ning Song; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2025)

Purple sweet potato anthocyanin-g-dialdehyde locust bean gum: An innovative polymeric colorant with good stability and application potential in food intelligent packaging - Dawei Yun; Huimin Yong; Fengfeng Xu; Ning Li; Tianzhu Guan; Jun Liu (Food Hydrocolloids, 2025)

Eriocheir sinensis CD63 activate mitochondria-mediated apoptosis to resist Spiroplasma eriocheiris infection - Wenbo Li; Guanzheng Yang; Yangzhi Fan; Xinru Yan; Zhuoqing Li; Ying Guo; Qing Wang; Xuguang Li; Wei Gu; Mingxiao Ning; Jun Zhou; Qingguo Meng (Fish & Shellfish Immunology, 2025)

Gas permeability and microscopic mechanisms of Xanthan gum-amended compacted lean clay as a gas barrier material - Ying-Zhen Li; Jia-Lei Wan; Fei Jin; Krishna R. Reddy; Ning-Jun Jiang; Yan-Jun Du (Engineering Geology, 2025)

Atmospheric CO2 and CH4 observations in Hangzhou before, during, and after the 2023 Asian Games: Insights from vehicle-carried and fixed stations - Tianhao Wang; Jiansen Wang; Ning Hu; Ruonan Li; Meng Shan; Qun Lin; Longlong Chen; Jun Wang; Yuxin Jiang; Zhonghao Yang; Wei Xiao (Atmospheric Pollution Research, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Identification and stability of QTLs for grain traits in the elite wheat variety ‘Chuanmai104’ - Zehou Liu; Hao Tang; Yuanyuan Lin; Xiaojiang Guo; Huixue Dong; Li Cai; Ying Liu; Qin Wang; Hongshen Wan; Fan Yang; Ning Yang; Jirui Wang; et al. (Cereal Research Communications, 2025)

Potential links between the progress in environmental governance and the prevalence of mental disorder burden: New insight from a dynamic panel-data analysis for 197 countries - Jun-Yan Xi; Li-Chang Chen; Xue-Qi Li; Jie Hu; Wei Hu; Jian-Jun Bai; Yi-Ning Xiang; Yu-Can Zhang; Jia-Jia Wang; Shi-Hao Wang; Jing Gu; Yuan-Tao Hao; et al. (Sustainable Cities and Society, 2025)

Fabrication of flexible polymer-MOF composite electrolyte for solid-state lithium metal batteries with high rate performance - Jiansheng Gao; Yan Chai; Jialun Ni; Yong Zeng; Gaoyuan Zhang; Xueling Liu; De Ning; Xinghui Jin; Huajun Zhao; Dong Zhou; Rui Gao; Wei Wu; et al. (Chemical Engineering Journal, 2025)

Carbon, hydrogen, nitrogen and chlorine isotope fractionation during 3-chloroaniline transformation in aqueous environments by direct photolysis, TiO2 photocatalysis and hydrolysis - Ning Min; Jun Yao; Hao Li; Steffen Kümmel; Thomas Schaefer; Hartmut Herrmann; Hans Hermann Richnow (Water Research, 2025)

Stalagmite multi-proxy records reveal spatial complexity of precipitation and monsoon variability in China over past 60 years - Yan-Xia Xue; Yao Wu; Chao-Jun Chen; Tao Fan; Huai Su; Han-Ying Li; Hai Cheng; Jian-Jun Yin; Jun-Yun Li; You-Feng Ning; Ting-Yong Li (Quaternary Science Reviews, 2025)

Adsorption of polycyclic aromatic hydrocarbons (PAHs) in soil and water on pyrochars: A review - Lishi Tang; Panpan Wang; Chengze Yu; Ning Jiang; Jiaqi Hou; Jun Cui; Shuaishuai Xin; Yanjun Xin; Mingxiao Li (Journal of Environmental Chemical Engineering, 2025)

Developing the sensing mechanism of high-performance N2H4 sensors derived from waste cotton stalk using a one-step process - Ping Hu; Jun Sun; Bo Ran; Jialin Li; Jialu Fang; Qihua Sun; Ning Tian; Zhaofeng Wu; Haiming Duan (Chemical Engineering Journal, 2025)

Decidual mesenchymal stem cells derived extracellular vesicles regulate ferroptosis to alleviate intervertebral disc degeneration through the HIF-1α signaling pathway - Miaojie Fang; Yuxian Wang; Zhenyu Li; Zilong Li; Yucheng Xue; Yiwen Xu; Kelei Wang; Hong Liu; Zhenzhong Chen; Wangmi Liu; Zhan Wang; Jun Li; et al. (Chemical Engineering Journal, 2025)

Mink enteritis virus infection induced cell cycle arrest and autophagy for its replication - Dong Lu-jiao; Li Zhi-juan; Sun Ying-Li; Fan Hua; Li Wen-qian; Zhang Hui-ning; Peng Jun; Xie Zhi-jing (Veterinary Microbiology, 2025)

Engineering injectable composite scaffolds for enhanced bone healing: Integration of stem cells, hydrogels, and microspheres - Hongda Wang; Junjin Li; Haiwen Feng; Huaying Hao; Jie Ren; Yuanquan Li; Chuanhao Li; Junyu Chen; Chao Sun; Jun Liang; Guangzhi Ning; Shiqing Feng (Chemical Engineering Journal, 2025)

Adaptive responses of Alicyclobacillus acidoterrestris in acidic broth and fruit juices: Focus on the influences of organic acids and temperature conditions - Ning Zhao; Yi Zhang; Jun Li; Junnan Xu; Lingxia Jiao; Kaidi Hu; Qin Li; Jianlong Li; Aiping Liu; Mingtao Fan; Shuliang Liu (International Journal of Food Microbiology, 2025)

Sensitive and portable intelligent detection platform construction and dietary risk assessment of procymidone in Chinese leek, cowpea and celery - Binbin Zhang; Shi Li; Wentao Zhang; Youpu Cheng; Zhenjiang Liu; Ning Zhang; Jun Xu; Xiaohu Wu; Fengshou Dong; Yongquan Zheng; Xinglu Pan (Food Chemistry, 2025)

Research progress of chlorine corrosion resistance in seawater electrolysis: Materials and technologies - Li-Juan Yang; Hao-Yue Guan; Shuo Yuan; Tao Sun; An-Ning Jiang; Ji-Jun Feng (Chemical Engineering Journal, 2025)

gCMEbox: A MATLAB toolbox for extracting and analyzing common-mode errors from GNSS time series - Shuangcheng Zhang; Jun Li; Lijiang Zhao; Anmin Zeng; Feng Ming; Ning Liu; Xiongchuan Chen; Zhijie Feng; Hengli Wang (Advances in Space Research, 2025)

Pyridoxine supplementation before puberty ameliorates MAM-induced cognitive and sensorimotor gating impairments - Cheng Xue; Xiao-Hui Li; Hong-Qun Ding; Xin Qian; Meng-Yu Zhang; Kai Chen; Zi-Wei Wei; Ying Li; Jun-Hai Jia; Wei-Ning Zhang (Metabolic Brain Disease, 2024)

Apoc1 Knockdown Alleviates High Glucose-induced Oxidative Stress and Apoptosis of Renal Tubular Cells by Binding to Clusterin - Liyin Chai; Zhengyang Liu; Jun Zeng; Li Gong; Sha Xiang; Jing Yu; Haili Sun; Chaolin Wen; Fang Wang; Ning Li; Bingbing Shen; Mei Mei (Cell Biochemistry and Biophysics, 2024)

Activation potential decreasing of iron oxide/graphite felt cathode by introducing Mn in electrochemical Fenton-like reactions - Yalong Xu; Weijian Li; Jun Wang; Di Wu; Ning Li; Yang Li; Xiaobin Fan; Wenchao Peng (Chemosphere, 2024)

Remediation of multi-metal(loid) contaminated soils using Mn-modified biochar: Mechanistic insights and influencing factors - Jin-Zhou Su; Xiao-Ning Feng; Ping Xiang; Zhao-Lai Guo; Li-Xin Li; Tao Zhang; Jun-Bao Yu (Process Safety and Environmental Protection, 2024)

Volatilomics of Cabernet Sauvignon grapes and sensory perception of wines are affected by canopy side in vineyards with different row orientations - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Hui-Qing Li; Ming-Yu Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Andrea Schubert; Jun Wang (Food Chemistry, 2024)

Vine tea kombucha ameliorates non-alcoholic fatty liver disease in high-fat diet fed mice via antioxidation, anti-inflammation and regulation of gut microbiota - Jin Cheng; Si-Yu Huang; Ruo-Gu Xiong; Si-Xia Wu; Zhi-Jun Yang; Dan-Dan Zhou; Adila Saimaiti; Cai-Ning Zhao; Hui-Lian Zhu; Hua-Bin Li (Food Bioscience, 2024)

Lightweight and superamphiphobic silanized cellulose–silica aerogels on green flexible thermal substrates - Kangkang Zhang; Lin Liu; Xian Wang; Junjie Shi; Ning Li; Yuxi Huang; Chunwang Yang; Susu Yang; Changzhao Li; Hao Lu; Hejin Liu; Jun Li; et al. (Chemical Engineering Journal, 2024)

A medicine and food homology formula prevents cognitive deficits by inhibiting neuroinflammation and oxidative stress via activating AEA–Trpv1–Nrf2 pathway - Ming-Jie Li; Jing-Yi Xu; Hua-Yue Zhang; Min Guo; Meng-Ning Lan; Jie Kong; Shi-Wei Liu; Hua-Jun Zheng (Inflammopharmacology, 2024)

CORS station for synergistic monitoring of multivariate surface parameters in expansive soils - Xiongchuan Chen; Shuangcheng Zhang; Yong Fang; Bin Wang; Ning Liu; Ningkang An; Jun Li; Zhijie Feng; Sijiezi Li (Advances in Space Research, 2024)

Application of high-precision gravity in fracture identification: a case study of the Miquan region of the Junggar Basin - Ning Jiang; Zhu-qiang Li; Yin Wang; Yi Bao; Jun Wang (Applied Geophysics, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Unravelling the nature differences of halide anions affecting the sorption of U(VI) by hydrous titanium dioxide supported waste polyacrylonitrile fibers in the presence of carbonates - Cheng Wang; Jun Liu; Bingtao Gui; Chao Li; Junxiang Shu; Shuwen An; Changsong Zhao; Juan Zhai; Ning Liu; Tu Lan (Science of The Total Environment, 2024)

Distributed extended state observer based formation tracking control of under-actuated unmanned surface vehicles with input and state quantization - Yifan Ma; Jun Ning; Tieshan Li; Lu Liu (Ocean Engineering, 2024)

Expanded PAH analysis of household air pollution in a rural region of China with high lung cancer incidence - Yongliang Zhang; Kees Meliefste; Wei Hu; Lützen Portengen; Nathaniel Rothman; Boris Reiss; Jihua Li; Jun Xu; Baofu Ning; Dingyu Liu; Flemming R. Cassee; Jason Y.Y. Wong; et al. (Environmental Pollution, 2024)

Bioaerosols emission from source facilities in a wastewater treatment plant: Critical exposure time and sensitivity analysis - Yi-ning Hu; Wei-di Wan; Jun-ting Wu; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zhe-ren Tang; Cheng-yun Wang; Cheng Yan (Environmental Pollution, 2024)

Salinomycin, a potent inhibitor of XOD and URAT1, ameliorates hyperuricemic nephropathy by activating NRF2, modulating the gut microbiota, and promoting SCFA production - Yong-jun Chen; Zi-tao Guo; Hai-qiao Chen; Shi-fan Zhang; Ying-xia Bao; Zhoufan Xie; Jia-le Ke; Wen-jie Ye; Jia-cheng Liang; Jia-chen Chen; Ning Li; Feng-xin Zheng; et al. (Chemico-Biological Interactions, 2024)

Comparative transcriptome analysis reveals the immune defense mechanism of the red swamp crayfish (Procambarus clarkii) in response to Vibrio parahaemolyticus challenge - Xiang Lu; Sheng Tang; Xin Liu; Jun-Jie Jiang; Dan-Dan Bian; Dai-Zhen Zhang; Qiu-Ning Liu; Yong-Xu Cheng; Bo-Ping Tang; Li-Shang Dai (Aquaculture, 2024)

Isobavachin induces autophagy-mediated cytotoxicity in AML12 cells via AMPK and PI3K/Akt/mTOR pathways - Ning Xia; Qing-Hai Chen; Zhao-Jun Meng; Shu-Yue Ma; Jia-Li Huang; Rong Shen; Yu-Tong Dong; Hai-Wei Du; Kun Zhou (Toxicology in Vitro, 2024)

Uptake of zinc from the soil to the wheat grain: Nonlinear process prediction based on artificial neural network and geochemical data - Kai-Ning Lv; Yong Huang; Guo-Li Yuan; Yu-Chen Sun; Jun Li; Huan Li; Bo Zhang (Science of The Total Environment, 2024)

Corrigendum to “Experimental investigation on hydrodynamic interaction between tsunami waves and bridge girder” [Ocean Eng. 294 (15 February 2024), 116683] - Shaolin Yang; Zhiqiang Tan; Wanli Yang; Jun Luo; Ning Wang; Jun Li; Riran Wang (Ocean Engineering, 2024)

An accurate and efficient forecast framework for fine PM2.5 maps using spatiotemporal recurrent neural networks - Ning Liu; Bin Zou; Yi Li; Zengliang Zang; Shan Xu; Sha Li; Shenxin Li; Lu Zhi; Jun Chen; Fang Zhao (Journal of Cleaner Production, 2024)

Transformation of dissolved nitrogen under UV/H2O2: A review on composition, behavior and potential risk - Yongsui Xu; Ning Yang; Sicheng Gong; Haoyu Guo; Jiawei Liu; Li Zhen; Zizhen Wu; Zhilin Zhang; Jia Liu; Jun Shi; Huiping Deng (Journal of Environmental Chemical Engineering, 2024)

Metabolomics of Vitis davidii Foëx. grapes from southern China: Flavonoids and volatiles reveal the flavor profiles of five spine grape varieties - Ning Shi; Xuan-Xuan Pei; Ming-Yu Li; Wen-Ting Chen; Hui-Qing Li; Guo-Shun Yang; Chang-Qing Duan; Jun Wang (Food Chemistry, 2024)

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

A reverberating triple AND logic gate nanomachine for intracellular multi-enzyme tracking and MicroRNA detection - Xu Zhu; Jun Zhu; Jin Wang; Guoquan Wu; Tianyu Su; Liying Fan; Junjie Li; Yufan Liu; Dehong Yu; Rongrong Sun; Ning Xin; Fenglei Gao (Chemical Engineering Journal, 2024)

Nicotinamide Riboside Promotes the Proliferation of Endogenous Neural Stem Cells to Repair Spinal Cord Injury - Jianping Zhang; Jun Shang; Han Ding; Wenxiang Li; Zonghao Li; Zhongze Yuan; Han Zheng; YongFu Lou; Zhijian Wei; Hengxing Zhou; Shiqing Feng; Xiaohong Kong; et al. (Stem Cell Reviews and Reports, 2024)

Safety, pharmacokinetics, and food-effect of pivmecillinam after single- and multiple-dose in healthy Chinese subjects: a phase I study - Lu-Lu Zhang; Yi Liu; Qiong-Ye Huang; Hong-Wen Zhang; Li-Jun Xie; Juan Chen; Li Ding; Chen Zhou; Lu-Ning Sun; Yong-Qing Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Occurrence, distribution, and ecological risks of antibiotics and antibiotic resistance genes in the surface waters of Gaoyou Lake, China - Xiaojian Xu; Chao Yang; Li Zou; Jun Leng; Ning Wang; Jing Zhang (Environmental Monitoring and Assessment, 2024)

Disturbance observer based adaptive trajectory tracking control for Unmanned Surface Vehicle with input and state quantization - Yu Wang; Wei Li; Jun Ning; Lu Liu (Ocean Engineering, 2024)

Effects of soil metal(loid)s pollution on microbial activities and environmental risks in an abandoned chemical smelting site - Hao Li; Jun Yao; Jianli Liu; Ning Min; Geoffrey Sunahara; Dongyang Men; Robert Duran (Journal of Environmental Sciences, 2024)

Volatomic differences among Vitis amurensis cultivars and its hybrids with V. vinifera revealed the effects of genotype, region, and vintage on grape aroma - Ming-Yu Li; Xuan-Xuan Pei; Ning Shi; Yi-Ming Yang; Shu-Tian Fan; Yan-Feng Sun; Qing-Sen Kong; Chang-Qing Duan; Keji Yu; Jun Wang (Food Research International, 2024)

Reliable detection of malachite green by self-assembled SERS substrates based on gold–silicon heterogeneous nano pineapple structures - Yu-ning Liu; Jian-jun Li; Guo-jun Weng; Jian Zhu; Jun-wu Zhao (Food Chemistry, 2024)

Smartphone-assisted mobile fluorescence sensor for self-calibrated detection of anthrax biomarker, Cu2+, and cysteine in food analysis - Sheng Wang; Jun Xu; Fengzhi Yue; Lina Zhang; Ning Bi; Jian Gou; Yongxin Li; Yuanyuan Huang; Tongqian Zhao; Lei Jia (Food Chemistry, 2024)

Experimental and numerical study on seismic performance of assembled platform canopy with mortise-tenon joints - Yu-zhen Chang; Jiu-yi Kuang; Chong Bai; Yu-jun Cai; Dan-ning Wang; Yuan Wang; Li-min Tian (Soil Dynamics and Earthquake Engineering, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Soil improvement using biostimulated MICP: Mechanical and biochemical experiments, reactive transport modelling, and parametric analysis - Yi-jie Wang; Wen-bo Chen; Peng-lin Li; Zhen-yu Yin; Jian-hua Yin; Ning-jun Jiang (Computers and Geotechnics, 2024)

Step-by-step transfer of photoexcited electron in donor-acceptor-catalyst configuration covalent triazine framework for efficient photoreduction CO2 to formic acid - Wei He; Wenhua Xu; Dengmeng Song; Jing Yang; Jing Zhou; Chengbo Li; Yong Yang; Jun Li; Ning Wang (Chemical Engineering Journal, 2024)

A blue light 3D printable hydrogel with water absorption, antibacterial, and hemostatic properties for skin wound healing - Xiu-Chong He; Xiu-Ning Chen; Yi-Hao Liu; Xinyu Zhong; Lei Qiang; Hong-Qin Wang; Fang-Zhou Wang; Jun-Song Wang; Cheng-Hui Li; Peng-Fei Zheng (Chemical Engineering Journal, 2024)

HDAC inhibitors as a potential therapy for chemotherapy-induced neuropathic pain - Chalton Manengu; Chun-Hao Zhu; Guo-Dong Zhang; Miao-Miao Tian; Xiao-Bing Lan; Li-Jun Tao; Lin Ma; Yue Liu; Jian-Qiang Yu; Ning Liu (Inflammopharmacology, 2024)

Adiponectin attenuates H2O2-induced apoptosis in chicken skeletal myoblasts through the lysosomal-mitochondrial axis - Han Wang; Chi Li; Longbo Zhu; Zhengqun Liu; Ning Li; Zi Zheng; Shiyue Liang; Jun Yan (In Vitro Cellular & Developmental Biology - Animal, 2024)

Considering the bioavailability and bioaccessibility of metal(loid)s for risk assessment of soils affected by different non-ferrous metal activities in Southwest China - Hao Li; Jun Yao; Ning Min; Geoffrey Sunahara; Yan Zhao; Robert Duran (Journal of Hazardous Materials, 2024)

Complete genome sequence and genetic characterization of a novel segmented RNA virus infecting Nilaparvata lugens - Chao Ning; Zhuang-Xin Ye; Zhong-Tian Xu; Ting Li; Chuan-Xi Zhang; Jian-Ping Chen; Jun-Min Li; Qianzhuo Mao (Archives of Virology, 2024)

Adaptive Distributed Heterogeneous Formation Control for UAV-USVs with Input Quantization - Jun Ning; Yuyang Huang; Zihan Liu; Wei Li; Xingwang Yue (Journal of Marine Science and Engineering, 2024)
This paper investigates the cooperative formation trajectory tracking problem for heterogeneous unmanned aerial vehicle (UAV) and multiple unmanned surface vessel (USV) systems with input quantization performance. Firstly, at the kinematic level, a distributed guidance law based on an extended state observer (ESO) is designed to compensate for the unknown speed of neighbor agents for expected trajectory tracking, and subsequently at the dynamic level, an ESO is utilized to estimate model uncertainties and environmental disturbances. Following that, a linear analytic model is employed to depict the input quantization process, and the corresponding adaptive quantization controller is designed without necessitating prior information on quantization parameters. Based on the input-to-state stability, the stability of the proposed control structure is proved, and all the signals in the closed-loop system are ultimately bounded. Finally, a simulation study is provided to show the efficacy of the proposed strategy.

NLRP3 inflammasome activation triggers severe inflammatory liver injury in N, N-dimethylformamide-exposed mice - Xiu-Ning Zhang; Yan-Jing Zhang; Lin Wang; Shu-Jun Hong; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2024)

Effect of dulcitol on growth performance, antioxidant activity, immune function, and intestinal microflora of growing-finishing pigs - Zhengqun Liu; Shiyue Liang; Diankui Wang; Zi Zheng; Ning Li; Chunhua Zhang; Jun Yan; Renmin Liu; Pei He; Qianjun Li; Shuqin Mu (Livestock Science, 2024)

Quantitative analysis of the numerical simulation uncertainties from geological models in CO2 geological storage: A case study of Shenhua CCS project - Huanwei Shi; Jun Li; Haolong Shen; Xiaochun Li; Ning Wei; Yongsheng Wang; Yan Wang; Huanquan Pan (International Journal of Greenhouse Gas Control, 2024)

Subregions of the fusiform gyrus are differentially involved in the attentional mechanism supporting visual mental imagery in depression - Jun-He Zhou; Bin-Kun Huang; Di Wang; Bai-Le Ning; Xue-Song Liang; Chang-Hong Li; Zeng-Jian Wang; Ying Deng; Xi-Chang Huang; De-Long Zhang; Wen-Bin Fu (Brain Imaging and Behavior, 2024)

Effect of sludge redistribution strategy on stability of partial nitrification-anammox process: Further exploration of the potential value of sludge - Peng Wang; Rui Ou; Jun Tan; Ning Li; Min Zheng; Qinghai Jin; Jin Yu; Di He (Chemosphere, 2024)

Microbial mechanisms of C/N/S geochemical cycling during low-water-level sediment remediation in urban rivers - Wen-Long Chen; Min Zhang; Jian-Guo Wang; Wei-Jie Huang; Qiong Wu; Xiao-Ping Zhu; Ning Li; Qian Wu; Wei Guo; Jun Chen (Journal of Environmental Management, 2024)

A sensitive fluorometric-colorimetric dual-mode intelligent sensing platform for the detection of formaldehyde - Xiangzhen Chen; Jun Xu; Lina Zhang; Ning Bi; Jian Gou; Yongxin Li; Tongqian Zhao; Lei Jia (Food Chemistry, 2024)

Correction to: BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2024)

Middle to late Holocene hydroclimate instability in the Yangtze River Delta region of China inferred from phytolith records, and its implications for societal disruption - Li Xueming; Liu Yan; Jiang Jun; Dai Jinqi; Xiao Li; Zhang Xiaoyu; Zhao Xiaoshuang; Chen Jing; Liu Shihao; Zhao Ning; Sun Qianli (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Photocatalysis uranium (VI) reduction at Cu2O/WO3|FTO Z-scheme heterojunction systems - Ning Liu; Hongsen Zhang; Jiahui Zhu; Qi Liu; Jing Yu; Rongrong Chen; Ying Li; Rumin Li; Jun Wang (Journal of Environmental Chemical Engineering, 2024)

How do contributions of organizations impact data inequality in OpenStreetMap? - Anran Yang; Hongchao Fan; Qingren Jia; Mengyu Ma; Zhinong Zhong; Jun Li; Ning Jing (Computers, Environment and Urban Systems, 2024)

Effects of different ecological restoration methods on the soil bacterial community structure of a light rare earth tailings pond - Tianyu Chen; Ning Qu; Jinxiao Wang; Yaochen Liu; Jiao Feng; Shilei Zhang; Chunying Xu; Zhiquan Cao; Jun Pan; Chunlin Li (Plant and Soil, 2024)

Distinct toxic effects, gene expression profiles, and phytohormone responses of Polygonatum cyrtonema exposed to two different antibiotics - Guoqun Yang; Dong Jiang; Li-Jun Huang; Chuantong Cui; Runke Yang; Xin Pi; Xia Peng; Xiaofeng Peng; Jianhui Pi; Ning Li (Journal of Hazardous Materials, 2024)

Unveiling the toxic effects, physiological responses and molecular mechanisms of tobacco (Nicotiana tabacum) in exposure to organic ultraviolet filters - Dong Jiang; Guoqun Yang; Li-Jun Huang; Kebin Chen; Yangcan Tang; Xin Pi; Runke Yang; Xia Peng; Chuantong Cui; Ning Li (Journal of Hazardous Materials, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Newcastle disease virus suppresses antigen presentation via inhibiting IL-12 expression in dendritic cells - Fulong Nan; Wenlong Nan; Xin Yan; Hui Wang; Shasha Jiang; Shuyun Zhang; Zhongjie Yu; Xianjuan Zhang; Fengjun Liu; Jun Li; Xiaoqiong Zhou; Delei Niu; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Heterogeneous metal sources for mintage in the early Han empire, second century BCE: archaeometallurgical study of the Banliang coins from the Guanghuacun cemetery, Chengdu, Southwest China - Ding Ma; Ning Wang; Pei Li; Tao Yang; Jun Yang; Ruizhe Wang; Wugan Luo (Archaeological and Anthropological Sciences, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Effects of different ecological restoration methods on the soil physicochemical properties and vegetation community characteristics of the Baotou light rare earth tailings pond in Inner Mongolia, China - Tianyu Chen; Ning Qu; Jinxiao Wang; Yaochen Liu; Jiao Feng; Shilei Zhang; Chunying Xu; Zhiquan Cao; Jun Pan; Chunlin Li (Environmental Science and Pollution Research, 2024)

The immune response of Caspase-3 gene in infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection of Litopenaeus vannamei - Cai-Yi Chen; Ning Yang; Chuanyu He; Yang Gao; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan (Aquaculture, 2024)

Experimental investigation on hydrodynamic interaction between tsunami waves and bridge girder - Shaolin Yang; Zhiqiang Tan; Wanli Yang; Jun Luo; Ning Wang; Jun Li; Riran Wang (Ocean Engineering, 2024)

Degradation of n-hexane by the high-throughput double dielectric barrier discharge: Influencing factors, degradation mechanism and pathways - Ke Li; Ning Jiang; Xiuwen Zhang; Kai Chen; Na Liu; Anton Nikiforov; Jun Chen; Zhiping Ye (Journal of Environmental Chemical Engineering, 2024)

Optimization of a QuEChERS–LC–MS/MS method for 51 pesticide residues followed by determination of the residue levels and dietary intake risk assessment in foodstuffs - Youzhi Su; Jianjiang Lu; Jun Liu; Fang Li; Ning Wang; Hongqin Lei; Xiaofang Shen (Food Chemistry, 2024)

Preparation of CPVC-based activated carbon spheres and insight into the adsorption-desorption performance for typical volatile organic compounds - Ning Dong; Ze Wang; Jun Wang; Wenli Song; Lin Du; Xiangyu Gu; Songgeng Li (Environmental Pollution, 2024)

Unveiling the mechanism of electrocatalytic oxidation of glycerol by in-situ electrochemical spectroscopy - Lixiong Xu; Yifan Yang; Chenyue Li; Rongqian Ning; Jun Ma; Mengqin Yao; Shuo Geng; Fei Liu (Chemical Engineering Journal, 2024)

The role of corneal endothelium in macular corneal dystrophy development and recurrence - Bi-Ning Zhang; Benxiang Qi; Chunxiao Dong; Bin Zhang; Jun Cheng; Xin Wang; Suxia Li; Xiaoyun Zhuang; Shijiu Chen; Haoyun Duan; Dewei Li; Sujie Zhu; et al. (Science China Life Sciences, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Aspartic acid/arginine enhance the stability of gelatin emulsions - Hui-min Yan; Yu Song; Man-man Yu; Xiu-ning Yao; Wen-wen Zhang; Ying Xu; Xue-qing Li; Yu-qin Xu; Shun Fang; Jun Qi; Guo-yuan Xiong; Chao Li; et al. (Journal of Food Engineering, 2024)

Twelve pathways of carbon neutrality for industrial parks - Yuheng Sun; Yuanhang Li; Jun Ning; Hang Fu; Fangtao Liu; Zhengyuan Feng; Guangxin Liu; Lei Shi (Journal of Cleaner Production, 2024)

Effects of Water Saturation and Loading Condition on Rock Tensile Strength: Insights from Acoustic Emission Analysis - Jun Zhu; Jianhui Deng; Po Ning; Ziguo Fu; Xuankun Li; Ronald Y. S. Pak (Rock Mechanics and Rock Engineering, 2024)

Identification of antibiotic resistant bacteria communities and a GeoChip based study of resistome in Fusarium wilt diseased and healthy soil - Haiyan Wu; Shanguo Chen; Lin Zhu; Yifei Xu; Jing Li; Ning Ling; Jun Yuan; Chao Xue; Qirong Shen (Applied Soil Ecology, 2024)

Formation Control for UAV-USVs Heterogeneous System with Collision Avoidance Performance - Yuyang Huang; Wei Li; Jun Ning; Zhihui Li (Journal of Marine Science and Engineering, 2023)
This paper investigates the cooperative formation trajectory tracking problem for heterogeneous unmanned aerial vehicle (UAV) and multiple unmanned surface vessel (USV) systems with collision avoidance performance. Firstly, a formation control protocol based on extended state observer (ESO) is proposed to ensure that the UAV and the USVs track the target trajectory simultaneously in the XY plane. Then, the collision avoidance control strategy of USV formation based on artificial potential field (APF) theory is designed. Specifically, the APF method is improved by reconstructing the repulsive potential field to make the collision avoidance action of USVs more in line with the requirements of International Regulations for Preventing Collisions at Sea (COLREGs). Following that, an altitude controller for the UAV is proposed to maintain the cooperative formation of the heterogeneous systems. Based on the input-to-state stability, the stability of the proposed control structure is proven, and all the signals in the closed-loop system are ultimately bounded. Finally, a simulation study is provided to show the efficacy of the proposed strategy.

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

Fe-MMT/WO3 composites for chemical and photocatalysis synergistic reduction of uranium (VI). - Ning Liu; Jing Yu; Hongsen Zhang; Jiahui Zhu; Qi Liu; Rongrong Chen; Ying Li; Rumin Li; Jun Wang (Chemosphere, 2023)

Carbon and hydrogen isotope fractionation of phthalates during photocatalysis reactions in aqueous solution containing Fe(III) complexes or iron minerals - Ning Min; Jun Yao; Hao Li; Junjie Zhu; Steffen Kümmel; Oliver J. Lechtenfeld; Thomas Schaefer; Hartmut Herrmann; Hans Hermann Richnow (Water Research, 2023)

Three new flavones from the whole plants of Cassia auriculata Linn. and their antiviral activities - Rui-Feng Xiong; Jun-Na Zheng; Qing-Yang Wu; Ning Jiang; Yuan-Sheng He; Yong-Jun Zhang; Ben-Hui Li; Wei Li; Qiu-Fen Hu; Zhen-Yuan Xia; Yin-Ke Li (Phytochemistry Letters, 2023)

Effects of polyethylene microplastics with different particle sizes and concentrations on the community structure and function of periphytic biofilms - Weiyu Li; Dan Luo; Ning Yan; Lingzhan Miao; Tanveer M. Adyel; Ming Kong; Jun Hou (Journal of Environmental Chemical Engineering, 2023)

Parental exposure to environmental cadmium causes developmental defects in the rare minnow (Gobiocypris rarus) embryos: The association between ROS-mediated oxidative stress and developmental dysfunction - Liangxia Su; Huanhuan Li; Yinrui Wu; Anni Tao; Ning Qiu; Rui Wang; Liu Jun; Jianwei Wang (Journal of Environmental Chemical Engineering, 2023)

Vineyard soil heterogeneity and harvest date affect volatolomics and sensory attributes of Cabernet Sauvignon wines on a meso-terroir scale - Hao-Cheng Lu; Meng-Bo Tian; Xiao Han; Ning Shi; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

Daily and seasonal patterns of stem diameter micro-variations in three semiarid forest species in relation to water status and environmental factors - Mei-Jun Liu; Qiu-Wen Chen; Hai-Ning Guo; Jinlin Lyu; Guoqing Li; Sheng Du (Dendrochronologia, 2023)

High negative voltage activating perovskite oxide with bi-vacancy synergistic regulation for water oxidation - Ning Yu; Yu Ma; Jing-Ke Ren; Zhi-Jie Zhang; Hai-Jun Liu; Jun Nan; Yi-Chuan Li; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2023)

Adsorption-desorption behaviors of ciprofloxacin onto aged polystyrene fragments in aquatic environments - Xiao-Yang Liu; Ning Wang; Long-Yi Lv; Peng-Fei Wang; Wen-Fang Gao; Li Sun; Guang-Ming Zhang; Zhi-Jun Ren (Chemosphere, 2023)

Fuzzy course tracking control of an unmanned surface vehicle with event-triggered mechanism and input quantization - Jun Ning; Yifan Ma; Lu Liu; Tieshan Li (Ocean Engineering, 2023)

Effects of fermented bamboo powder on growth performance, apparent digestibility, carcass traits, and meat quality in growing-finishing pigs - Zi Zheng; Zhengqun Liu; Ning Li; Shuqin Mu; Shiyue Liang; Zhonghao Liu; Chunhua Zhang; Yuanming Li; Jun Yan; Qianjun Li (Livestock Science, 2023)

Regioselective [3 + 2] cycloaddition of diazo reagents and internal alkynes: Accessing regiosomers of highly substituted trifluoromethylpyrazoles - Shuo-Han Li; Ran Guo; Ning Lv; Yu Liu; Xiaodong Tang; Jun-An Ma (Journal of Fluorine Chemistry, 2023)

Mechanisms on stability of bulk nanobubble and relevant applications: A review - Xuelin Wang; Pan Li; Rongsheng Ning; Rehman Ratul; Xianren Zhang; Jun Ma (Journal of Cleaner Production, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Improved yield-salinity relationship considering salt and root distribution dynamics - Yuehong Zhang; Xianyue Li; Jun Wang; Haibin Shi; Ning Chen; Qi Hu (European Journal of Agronomy, 2023)

Advances and promotion strategies of membrane-based methods for extracting lithium from brine - Yu-ning Zhang; De-hao Yu; Chen-yu Jia; Li-yue Sun; Ang Tong; Yao Wang; Yan-xin Wang; Lin-jun Huang; Jian-guo Tang (Desalination, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Carbon isotope fractionation of di-(2-ethylhexyl)-phthalate during photosensitized degradation by •OH and S O 4 · - for characterization of reaction mechanisms - Ning Min; Jun Yao; Hao Li; Junjie Zhu; Steffen Kümmel; Thomas Schaefer; Hartmut Herrmann; Hans Hermann Richnow (Chemical Engineering Journal, 2023)

Human amnion-derived mesenchymal stem cells improve subclinical hypothyroidism by immunocompetence mediating apoptosis inhibition on thyroid cells in aged mice - Chuyu Li; Qiang Rui; Xiaohan Dong; Song Ning; Jing Zhou; Huimin Wu; Chunyan Jiang; Yugui Cui; Jiayin Liu; Jun Jiang; Lianju Qin (Cell and Tissue Research, 2023)
Subclinical hypothyroidism (SCH) affects 10% of the global population, which is most prevalent in women and the elderly. However, it remains debatable whether the elderly with subclinical hypothyroidism needs thyroxine supplement. Human amnion-derived mesenchymal stem cells (hAMSCs) could play important roles in autoimmune diseases, suggesting that hAMSC be a candidate to regulate the thyroid function of female age-related subclinical hypothyroidism. Herein, we established the model of SCH in the aged female mice. This study was designed to investigate whether human amnion-derived mesenchymal stem cells (hAMSC) could effect on immune regulation, apoptosis inhibition of thyroid cells, thyroid function, blood lipid levels, and heart function. In addition, qualified hAMSCs were intravenously injected into aged female SCH mice via the tail vein on day 0 and day 10. The levels of thyroid hormone and blood lipids as well as cardiac function, serum immunological indexes, and apoptosis of thyroid cells were then analyzed on day 5, 10, 15, and 20; meanwhile, the quantity of Th1, Th2, Th17, and Treg immune cells in peripheral blood was evaluated before and on day 20 post-injection. Our study demonstrated that after hAMSC transplantation, the thyroid functions, blood lipid levels, and heart function indexes of age-related SCH (AR-SCH) mice were significantly improved. Consistent with this, Th1 and Treg cells increased significantly, while Th2 and Th17 cells decreased in peripheral blood. Apoptosis was also suppressed in the thyroid cells. In summary, hAMSC delivery can potentially be a safe and effective therapy for treating SCH in the elderly, improving related complications by immunomodulatory and apoptosis inhibition.

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

M1 polarization of chicken macrophage HD11 can be activated by duck Tembusu virus via MyD88-NF-κB-mediated signaling pathway - Ningwei Geng; Ji Fu; Zehao Lv; Jing Li; Yuxin Kong; Lei Qu; Zhiyun Guo; Jun Zhao; Liya Zhu; Feng Wang; Cui Zhao; Sidang Liu; et al. (Veterinary Microbiology, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Corrigendum to “Using Fe biofortification strategies to reduce both Ni concentration and oral bioavailability for rice with high Ni” [J Hazard Mater 452 (2023) 131367] - Xin-Ying Lin; Jia-Hui Liang; Duo-Duo Jiao; Jun-Xiu Chen; Ning Wang; Lena Q. Ma; Dongmei Zhou; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Microbial metabolic activity in metal(loid)s contaminated sites impacted by different non-ferrous metal activities - Hao Li; Jun Yao; Ning Min; Geoffrey Sunahara; Jianli Liu; Miaomaio Li; Bang Liu; Wancheng Pang; Ying Cao; Ruofei Li; Robert Duran (Journal of Hazardous Materials, 2023)

Defects influence photocatalytic NOCM product selectivity by controlling photogenerative carriers - Ning Zhang; Yu Fu; Wenbo Kong; Bingrong Pan; Changkun Yuan; Shuqing Li; He Zhu; Jun Zhang (Journal of Environmental Chemical Engineering, 2023)

A wearable gloved sensor based on fluorescent Ag nanoparticles and europium complexes for visualized assessment of tetracycline in food samples - Jun Xu; Junxi Wang; Yongxin Li; Lina Zhang; Ning Bi; Jian Gou; Tongqian Zhao; Lei Jia (Food Chemistry, 2023)

Mobile crowdsensing framework for drive-by-based dense spatial-resolution bridge mode shape identification - Zhen Peng; Jun Li; Hong Hao; Ning Yang (Engineering Structures, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

From arc accretion to within-plate extension: Geochronology and geochemistry of the Neoproterozoic magmatism on the northern margin of the Yangtze Block - Yu Huang; Xiao-Lei Wang; Jun-Yong Li; Ru-Cao Li; De-Hong Du; Chang-Hong Jiang; Lin-Sen Li; Ning Ding (Precambrian Research, 2023)

Phytochemistry and biological activities of corynanthe alkaloids - Jun Li; Jia-Xing Li; Hua Jiang; Min Li; Lin Chen; Yue-Yue Wang; Lu Wang; Ning Zhang; He-Zhe Guo; Kai-Long Ma (Phytochemistry, 2023)

Baicalin promotes antiviral IFNs production and alleviates type I IFN-induced neutrophil inflammation - Li Li; Jia-Min Dong; He-He Ye; Man-Jing Jiang; Huan-Hua Yang; Lin-Pan Liang; Li-Jun Ning; Ying Wu (Journal of Natural Medicines, 2023)

Cuproptosis-related gene SLC31A1 expression correlates with the prognosis and tumor immune microenvironment in glioma - Jun Wang; Shenglun Li; Yuduo Guo; Chao Zhao; Yujia Chen; Weihai Ning; Jingjing Yang; Hongwei Zhang (Functional & Integrative Genomics, 2023)
Cuproptosis is a newly discovered form of cell death. It is regulated by a string of genes. The genes are identified to influence the tumor progression, but in glioma, the cuproptosis-related genes are little studied. The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression (GTEx) were used to screen for SLC31A1 gene expression in glioma and healthy tissue samples. The results were validated using the Gene Expression Omnibus (GEO) and quantitative real-time polymerase chain reaction (qPCR). The Human Protein Atlas (HPA) and the National Cancer Institute’s Clinical Proteomic Tumor Analysis Consortium (CPTAC) were used to validate our results at the protein level. Multivariable analysis and Kaplan–Meier survival curves were used to examine the relationship among SLC31A1 gene expression, clinical parameters, and survival rates. The online Search Tool for the Retrieval of Interacting Genes/Proteins (STRING) was used to find the genes and proteins that correlate to SLC31A1 . The immune infiltration analysis was performed using the Tumor Immune Estimation Resource (TIMER) databases. Small interfering RNA was used to knock down the SLC31A1 expression, and the cell proliferation, apoptosis, and migration were analyzed using cell counting kit-8, flow cytometry, and transwell. The glioma patients have higher SLC31A1 expression levels, which increase as the World Health Organization (WHO) grade escalates. The survival analysis illustrates that the SLC31A1 gene expression negatively correlates with overall survival (OS), progression-free survival (PFS), and disease-specific survival (DSS). The immune infiltration analysis shows the SLC31A1 gene positively correlates with T helper 2 (Th2) cells, macrophages, and M2-type macrophages and negatively correlates with plasmacytoid dendritic cells (pDCs), natural killer (NK) CD56bright cells, and CD8 T cells. The in vitro KD experiment shows the SLC31A1 knockdown depressed the glioma cell proliferation and migration and promoted the apoptosis rate. The SLC31A1 gene expression can shorten the survival time of glioma patients. In vitro study shows that SLC31A1 can promote cell proliferation, and migration, and depress the cell apoptosis of glioma cells. It also can promote the formation of a tumor-suppressive microenvironment.

Distribution, sources, and risk assessment of polycyclic aromatic hydrocarbons (PAHs) in Kaokaowusu river sediments near a coal industrial zone - Zhu Wang; Yong Jun Liu; Lu Yang; Zhuang Zhuang Yang; Ai Ning Zhang; Zhi Hua Li; Zhe Liu (Environmental Geochemistry and Health, 2023)

Instability mechanism and stability control of gob-side entry in a deep mine: a case study - Shang Yang; Jianguo Ning; Mingtao Gao; Jun Wang; Xinshuai Shi; Shanchao Hu; Yanlei Li (Bulletin of Engineering Geology and the Environment, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Molecular insights into ions permeation and destruction behavior in methane hydrate driven by electrostatic fields - Jie Chen; Zhengcai Zhang; Yongchao Hao; Daniel Porfirio Luis Jiménez; Jiafang Xu; Nengyou Wu; Fulong Ning; Bin Fang; Jun Zhang; Jianye Sun; Xiluo Hao; Qingguo Meng; et al. (Fuel, 2023)

Contribution of amino acids to Alicyclobacillus acidoterrestris DSM 3922T resistance towards acid stress - Junnan Xu; Ning Zhao; Xuemei Meng; Tong Zhang; Jun Li; Huayu Dong; Xinyuan Wei; Mingtao Fan (Food Microbiology, 2023)

Investigation on the potential adverse outcome pathway of the sensitive endpoint for nephrotoxicity induced by gardenia yellow based on an integrated strategy using bioinformatics analysis and in vitro testing validation - Jiang Liang; Hong-Xin Wei; Ying-Ying Zhou; Li-Li Hao; Jun-Yu Ning; Lei Zhang (Food and Chemical Toxicology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Effect of the random distribution of gravel particles on the mechanical behaviors of conglomerate - Jun Wei; Hualin Liao; Bin Huang; Ning Li; Hongjun Liang; Bo Zhou; Quan Zhang; Long Chen; Hui Feng (Arabian Journal of Geosciences, 2023)

Graphene nano zinc oxide reduces the expression and release of antibiotic resistance-related genes and virulence factors in animal manure - Haibo Zhang; Weikun Guan; Jun Shu; Sen Yu; Yingmin Xiong; Gao Liu; Yuhong Zhong; Jia Chen; Zhigang Zhao; Ning He; Qingfeng Xing; Dongsheng Guo; et al. (Science of The Total Environment, 2023)

New insights on the effect of non-ferrous metal mining and smelting activities on microbial activity characteristics and bacterial community structure - Hao Li; Jun Yao; Ning Min; Geoffrey Sunahara; Robert Duran (Journal of Hazardous Materials, 2023)

Using Fe biofortification strategies to reduce both Ni concentration and oral bioavailability for rice with high Ni - Xin-Ying Lin; Jia-Hui Liang; Duo-Duo Jiao; Jun-Xiu Chen; Ning Wang; Lena Q. Ma; Dongmei Zhou; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Insights into the enhanced performance of NiCo-LDH modified Pd/NF cathode for electrocatalytic hydrodechlorination - Jingmin Wang; Xuefeng Wei; Peipei Wang; Juan Miao; Ruichang Zhang; Ning Zhang; Xinquan Zhou; Hang Xu; Jun Zhang; Haisheng Li; Shuge Peng (Fuel, 2023)

An integrated strategy combining network toxicology and feature-based molecular networking for exploring hepatotoxic constituents and mechanism of Epimedii Folium-induced hepatotoxicity in vitro - Zhen Zhao; Jin-Fa Du; Qiao-Lei Wang; Fang-Ning Qiu; Xu-Yan Chen; Feng-Jie Liu; Ping Li; Yan Jiang; Hui-Jun Li (Food and Chemical Toxicology, 2023)

Precisely mapping a major QTL for grain weight on chromosome 5B of the founder parent Chuanmai42 in the wheat-growing region of southwestern China - Meijin Ye; Hongshen Wan; Wuyun Yang; Zehou Liu; Qin Wang; Ning Yang; Hai Long; Guangbing Deng; Yumin Yang; Hong Feng; Yonghong Zhou; Cairong Yang; et al. (Theoretical and Applied Genetics, 2023)

Effects of Bacillus subtilis BS-Z15 on Intestinal Microbiota Structure and Body Weight Gain in Mice - Jun Yang; Huan-Chen Ning; Qi Zhang; Jun-Qi Yue; Xi-Yuan Cao; Jin-Yu Li; Ling Liu; He-Ping Zhao; Hui-Xin Zhao (Probiotics and Antimicrobial Proteins, 2023)

Quantifying ecological and human health risks of metal(loid)s pollution from non-ferrous metal mining and smelting activities in Southwest China - Hao Li; Jun Yao; Geoffrey Sunahara; Ning Min; Chenchen Li; Robert Duran (Science of The Total Environment, 2023)

Abundant rather than rare fungi perform a vital role in maintaining the growth of continuous cropped cut chrysanthemum - Rui Tao; Jun Li; Siqi Yu; Baowei Hu; Ning Ling; Guixin Chu (European Journal of Soil Biology, 2023)

Karst-ecological changes during the middle and late Holocene in Southwest China revealed by δ18O and δ13C records in a stalagmite - Rong Duan; Ting-Yong Li; Jun-Yun Li; Christoph Spötl; Hong-Chun Li; Hai-Bo Wang; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Jing-Li Zhou; Chao-Jun Chen; Tsai-Luen Yu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Influence of Lonicera japonica and Radix Puerariae crude extracts on the growth performance, antioxidant capacity, and immunological functions of finishing pigs - Zhonghao Liu; Jun Yan; Ning Li; Zi Zheng; Chunhua Zhang; Zhengqun Liu; Chunling Song; Shuqin Mu (Livestock Science, 2023)

Metagenomic analysis revealed the mechanism of extracellular polymeric substances on enhanced nitrogen removal in coupled MABR systems with low C/N ratio containing salinity - Zhiye Sun; Yi Li; Jianwei Yue; Zhongzhong Song; Ming Li; Ning Wang; Jun Liu; Hong Guo; Baoan Li (Journal of Environmental Chemical Engineering, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

Severe shoot topping slows down berry sugar accumulation rate, alters the vine growth and photosynthetic capacity, and influences the flavoromics of Cabernet Sauvignon grapes in a semi-arid region - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Xiao Han; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (European Journal of Agronomy, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

A novel intelligently integrated MOF-based ratio fluorescence sensor for ultra-sensitive monitoring of TC in water and food samples - Xiangzhen Chen; Jun Xu; Yongxin Li; Lina Zhang; Ning Bi; Jian Gou; Taofeng Zhu; Lei Jia (Food Chemistry, 2023)

Tomographic evidences for hydraulic fracturing induced seismicity in the Changning shale gas field, southern Sichuan Basin, China - Yuyang Tan; Jiawei Qian; Jun Hu; Haijiang Zhang; Huilin Xing; Junlun Li; Jian Xu; Wen Yang; Ning Gu; Siyu Miao (Earth and Planetary Science Letters, 2023)

Cinnamaldehyde affects lipid droplets metabolism after adipogenic differentiation of C2C12 cells - Yanrong Liu; Zhengqun Liu; Qiang Luo; Zhuwen Sun; Ning Li; Zi Zheng; Shuqin Mu; Xiaoqiao Zhou; Jun Yan; Chao Sun; Hongfu Zhang (Molecular Biology Reports, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Two new tetrahydroisoquinoline alkaloids from Portulaca oleracea - Kai-Jun Tang; Yu Chen; Jing Li; Xu Tao; Lu-Ping Yang; Tian-Yun Jin; Jia-Shun Zhu; Yu Zhao; Tao Shen; Xiao-Ning Wang; Dong-Mei Ren; Lan Xiang (Phytochemistry Letters, 2023)

Genetic characteristics and growth patterns of the hybrid grouper derived from the hybridization of Epinephelus fuscoguttatus (female) × Epinephelus polyphekadion (male) - Liu Cao; Pan Chen; Xingrong Hou; Jun Ma; Ning Yang; Yanping Xu; Yanjin Zhang; Anqi Zhao; Jiyuan Zhang; Xinyu Li; Hai Huang (Journal of Fish Biology, 2023)
Hybridization is one of the primary methods used to cultivate farmed grouper species. The hybrid grouper derived from crossing Epinephelus fuscoguttatus (♀) and E. polyphekadion (♂) exhibits growth superiority over its parents. The genetic characteristics and growth patterns of the hybrid grouper have not yet been defined. This study confirms the ploidy level of the hybrid grouper (2 n = 48) using chromosome count analysis and flow cytometry. The 5S rDNA family was used to evaluate genetic diversity. Only one 5S class (~400 bp) was detected in the hybrid grouper, which could be used to distinguish between two different types based on nucleotide sequences, likely representing homologous unit classes from the female and male parental species. Growth patterns of 5–8‐month‐old hybrid groupers were also monitored. In this phase, a positive allometric growth pattern in body mass with total length was found. Body height and body mass were significantly correlated based on correlation and path coefficient, suggesting that body height could serve as an excellent index to increase body mass. These results aid our understanding of the genetic evolution of the hybrid grouper and inform the development of improved rearing techniques.

Multi-radar data fusion for maritime moving target detection based on three-dimensional sliding window - He Wen; Yu Li; Chongdi Duan; Jun Zhang; Ning Li; Tao Wu (International Journal of Remote Sensing, 2023)

A basic investigation on evolution of CL-L1 in vertebrates and its bioactivities in black rockfish (Sebastes schlegelii) - Hui Jun Huo; Tian Zhen Yang; Qing Zhu; Ning Yang; Chao Li (Aquaculture, 2023)

A repeated dose 28-day oral toxicity study of sodium dehydroacetate (DHA-S) in Wistar rats - Hong-ju Du; Guo-hui Tong; Jun-yu Ning; Shan Gao; Qing Yang; Ying Feng; Peng Zhang; Wei Zhang; Hai-ming Jing; Guo-jun Li (Regulatory Toxicology and Pharmacology, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

Electrocatalytic hydrogenation of phenol by active sites on Pt-decorated shrimp shell biochar catalysts: Performance and internal mechanism - Xukai Lu; Jun Wang; Wenchao Peng; Ning Li; Lan Liang; Zhanjun Cheng; Beibei Yan; Gaixiu Yang; Guanyi Chen (Fuel, 2023)

Region, vintage, and grape maturity co-shaped the ionomic signatures of the Cabernet Sauvignon wines - Xiao Han; Hao-Cheng Lu; Yu Wang; Xiao-Tong Gao; Hui-Qing Li; Meng-Bo Tian; Ning Shi; Ming-Yu Li; Xiao-Li Yang; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

Ultrasonic-assisted stewing enhances the aroma intensity of chicken broth: A perspective of the aroma-binding behavior of fat - Jun Qi; Chuan-kang Jia; Wen-wen Zhang; Hui-min Yan; Qing-yuan Cai; Xiu-ning Yao; Kuo Xu; Ying Xu; Wen-ping Xu; Guo-yuan Xiong; Mei-qi Li (Food Chemistry, 2023)

Salt Bridge-intermediated three phase decoupling electrolytes for high voltage electrolytic aqueous Zinc-Manganese dioxides battery - Qi Xu; Qi-Xing Xie; Tong Xue; Gao Cheng; Jian-Dong Wu; Lan Ning; Xiang-Hui Yan; You-Jun Lu; Zhong-Li Zou; Bei-Ping Wang; Feng-Lan Han (Chemical Engineering Journal, 2023)

A mathematical model of critical releasable charge for R290 indoor leakage of split-type household air conditioners - Qian Ning; Guogeng He; Jun Xiong; Mingjing Fan; Xiao Li (Building and Environment, 2023)

Enhanced cellulosic d-lactic acid production from sugarcane bagasse by pre-fermentation of water-soluble carbohydrates before acid pretreatment - Zhongyang Qiu; Xushen Han; Anqing Fu; Yalan Jiang; Wenyue Zhang; Ci Jin; Dengchao Li; Jun Xia; Jianlong He; Yuanfang Deng; Ning Xu; Xiaoyan Liu; et al. (Bioresource Technology, 2023)

The increasing big gap of carbon sink between the western and eastern Pacific in the last three decades - Guorong Zhong; Xuegang Li; Jinming Song; Baoxiao Qu; Fan Wang; Yanjun Wang; Bin Zhang; Detong Tian; Jun Ma; Huamao Yuan; Liqin Duan; Ning Li; et al. (Frontiers in Marine Science, 2022)
The Pacific Ocean is one of the important carbon sink regions, and there is a significant west-east difference in sea-air CO 2 flux. However, the influence of the long-standing greater CO 2 uptakes in the western Pacific than in the east and the dynamic change of this west-east difference remain unclear. In this paper, using the gridded surface ocean p CO 2 product constructed by the stepwise FFNN algorithm, we reported an increasing west-east CO 2 flux difference from 0.41 PgC yr -1 in 1992 to 0.73 PgC yr -1 in 2020. This increase was mainly attributed to the strengthening western Pacific carbon sink and relatively stable eastern Pacific carbon source. During El Nino events, the west-east CO 2 flux difference decreased significantly in a few years, and it then rose back rapidly when El Nino events ended. In addition, the increasing west-east difference in CO 2 uptakes during the last three decades did not lead to a higher acidification speed in the western surface temperate Pacific than the east. The greater CO 2 absorbed in the west was mainly transported to the deeper waters and caused a more significant carbon inventory change at 200-600 m than the eastern Pacific.

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

The small RNA STnc1480 contributes to the regulation of biofilm formation and pathogenicity in Salmonella typhimurium - Jing Li; Chengcheng Ning; Na Li; Yun Guo; Chunhui Ji; Xiaozhen Zhu; Xingxing Zhang; Qingling Meng; Xianzhu Xia; Xuepeng Cai; Jun Qiao (Archives of Microbiology, 2022)

Crustal electrical structure across the Tangra-Yumco tectonic belt revealed by magnetotelluric data: new insights on the east–west extension mechanism of the Tibetan plateau - Ning Chen; Xuben Wang; Changsheng Shao; Jun Zou; Zhengwei Xu; Dewei Li; Xiangpeng Wang (Acta Geophysica, 2022)

CircHIPK3 promotes proliferation and metastasis of villous trophoblasts through miR-30a-3p/Wnt2 axis - Shuhong Li; Ning Li; Bing Li; Lili Zhu; Tingting Xu; Li Wang; Jun Zhang; Fanqiang Kong (Journal of Genetics, 2022)

Transcriptome analysis and co‐expression network reveal the mechanism linking mitochondrial function to immune regulation in red crucian carp ( Carassius auratus red var) after Aeromonas hydrophila challenge - Ning‐Xia Xiong; Xu‐Ying Kuang; Zi‐Xuan Fang; Jie Ou; Shi‐Yun Li; Jia‐Hui Zhao; Jin‐Fang Huang; Ke‐Xin Li; Rou Wang; Lan‐Fen Fan; Sheng‐Wei Luo; Shao‐Jun Liu (Journal of Fish Diseases, 2022)
Aeromonas hydrophila is a common pathogen of freshwater fish. In this study, A. hydrophila infection was shown to cause tissue damage, trigger physiological changes as well as alter the expression profiles of immune‐ and metabolic‐related genes in immune tissues of red crucian carp (RCC). Transcriptome analysis revealed that acute A. hydrophila infection exerted a profound effect on mitochondrial oxidative phosphorylation linking metabolic regulation to immune response. In addition, we further identified cellular senescence, apoptosis, necrosis and mitogen‐activated protein kinase signal pathways as crucial signal pathways in the kidney of RCC subjected to A. hydrophila infection. These findings may have important implications for understanding modulation of immunometabolic response to bacterial infection.

Oxytocin Receptor in Cerebellar Purkinje Cells Does Not Engage in Autism-Related Behaviors - Li-Ping Shen; Wei Li; Ling-Zhu Pei; Jun Yin; Shu-Tao Xie; Hong-Zhao Li; Chao Yan; Jian-Jun Wang; Qipeng Zhang; Xiao-Yang Zhang; Jing-Ning Zhu (The Cerebellum, 2022)

Synthesis and in vitro biological evaluation of novel dendrocandin analogue as potential anti-tumor agent - Jing-Yun Yan; Hao-Nan Yang; Ning Yang; Yin-Rong Xie; Xiu-Li Sun; Ye-Wei Huang; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Natural Product Research, 2022)

Identification and expression of potential olfactory-related genes related to Niemann–Pick C2 protein and ionotropic receptors in Haemaphysalis longicornis - Yingying Cui; Jungang Wang; Qiyong Liu; Dongmei Li; Wen Zhang; Xiaobo Liu; Jun Wang; Xiuping Song; Feng Yao; Haixia Wu; Ning Zhao (Experimental and Applied Acarology, 2022)

ArsZ from Ensifer adhaerens ST2 is a novel methylarsenite oxidase - Jun Zhang; Yan‐Ning Li; Jian Chen; Yu Yan; Barry P. Rosen; Fang‐Jie Zhao (Environmental Microbiology, 2022)
Summary Trivalent methylarsenite [MAs(III)] produced by biomethylation is more toxic than inorganic arsenite [As(III)]. Hence, MAs(III) has been proposed to be a primordial antibiotic. Other bacteria evolved mechanisms to detoxify MAs(III). In this study, the molecular mechanisms of MAs(III) resistance of Ensifer adhaerens ST2 were investigated. In the chromosome of E. adhaerens ST2 is a gene encoding a protein of unknown function. Here, we show that this gene, designated arsZ , encodes a novel MAs(III) oxidase that confers resistance by oxidizing highly toxic MAs(III) to relatively nontoxic MAs(V). Two other genes, arsRK , are adjacent to arsZ but are divergently encoded in the opposite direction. Heterologous expression of arsZ in Escherichia coli confers resistance to MAs(III) but not to As(III). Purified ArsZ catalyses thioredoxin‐ and NAPD + ‐dependent oxidation of MAs(III). Mutational analysis of ArsZ suggests that Cys59 and Cys123 are involved in the oxidation of MAs(III). Expression of arsZ , arsR and arsK genes is induced by MAs(III) and As(III) and is likely controlled by the ArsR transcriptional repressor. These results demonstrate that ArsZ is a novel MAs(III) oxidase that contributes to E. adhaerens tolerance to environmental organoarsenicals. The arsZRK operon is widely present in bacteria within the Rhizobiaceae family.

Anti-hyperglycaemic effect of labdane diterpenes isolated from the rhizome of Amomum maximum Roxb., an edible plant in Southwest China - Chuan-Li Lu; Li-Ning Wang; Ya-Jun Li; Qing-Fei Fan; Qing-Hua Huang; Jun-Jia Chen (Natural Product Research, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Population pharmacokinetics of valproic acid in adult Chinese patients with bipolar disorder - Yan-Nan Zang; Wei Guo; Meng-Xi Niu; Shuang Bao; Qian Wang; Yan Wang; Fang Dong; An-Ning Li; Can-Jun Ruan (European Journal of Clinical Pharmacology, 2022)

Association between maternal exposure to PM10 and risk of anorectal atresia/stenosis in offspring: a population-based case-control study in Liaoning Province, China - Tie-Ning Zhang; Qi-Jun Wu; Yan-Hong Huang; Jing Li; Zong-Jiao Chen; Li-Li Li; Yan-Ling Chen; Shu Liu; Cheng-Zhi Jiang; Yu-Hong Zhao (Environmental Science and Pollution Research, 2022)

Simulation of the pollution abatement behavior of regional metal-related enterprises based on the interactive perspective of industrial agglomerations and emission reduction effects - Li-Xin Xiong; Jia-Jun Ning; Yun-He Dong; Meng-Meng Dai (Environmental Geochemistry and Health, 2022)

Anti-Roll Characteristics of Marine Gyrostabilizer Based on Adaptive Control and Hydrodynamic Simulation - Biao Li; Xianku Zhang; Jun Wang; Ning Chen (Journal of Marine Science and Engineering, 2022)
The gyrostabilizer produces the anti-roll effect through the precession output moment generated by a high-speed rotating flywheel. As a floating-base multi-body system composed of ship and gyrostabilizer, the recent research that has only focused on the control strategies or multi-body dynamics is obviously not comprehensive. This study presents an adaptive controller based on the variable gain control strategy for a marine gyrostabilizer installed on a port salvage tug. The variable gain control strategy controlled the flywheel precession output moment of the gyrostabilizer and thereby of the precession process, to reduce the ship roll motion effectively. Furthermore, a full-system hydrodynamic model of a gyrostabilizer-ship-wave based on three-dimensional numerical wave flume technology was innovatively established to evaluate its anti-roll performance under irregular wave conditions. The simulation results show that, for the sea state considered, the increase of spin rate of gyrostabilizer flywheel improved the anti-roll effect significantly. The average anti-roll rate of the gyrostabilizer decreased with the increase of significant wave height, wave period and wave encounter angle.

Synthesis, characterization and antitumor mechanism investigation of ruthenium(II) polypyridyl complexes with artesunate moiety - Bi-Chun Chen; Jun-Jian Lu; Ning Jiang; Xiu-Rong Ma; Rong-Tao Li; Rui-Rong Ye (JBIC Journal of Biological Inorganic Chemistry, 2021)

Erratum to: Analysis of differences in nutrients chemistry in seamount seawaters in the Kocebu and M5 seamounts in Western Pacific Ocean - Jun Ma; Jinming Song; Xuegang Li; Qidong Wang; Huamao Yuan; Ning Li; Liqin Duan (Journal of Oceanology and Limnology, 2021)

Characteristics and biogeochemical effects of oxygen minimum zones in typical seamount areas, Tropical Western Pacific - Qidong Wang; Jinming Song; Xuegang Li; Jun Ma; Huamao Yuan; Ning Li; Liqin Duan (Journal of Oceanology and Limnology, 2021)

Analysis of differences in nutrients chemistry in seamount seawaters in the Kocebu and M4 seamounts in Western Pacific Ocean - Jun Ma; Jinming Song; Xuegang Li; Qidong Wang; Huamao Yuan; Ning Li; Liqin Duan (Journal of Oceanology and Limnology, 2021)

Baicalin attenuates adriamycin-induced nephrotic syndrome by regulating fibrosis procession and inflammatory reaction - Ning Tan; Chen-Xia Sun; Hui-Jun Zhu; De-Yu Li; Sheng-Guang Huang; Shou-Di He (Genes & Genomics, 2021)

Transcriptome analysis of wolf spider Pardosa laura exposed to beta-cypermethrin - Qing Ning; Jing Li; Li-hua Wang; Yu-jun Dai; Chang-chun Li (International Journal of Tropical Insect Science, 2021)

Utilizing multichannel electrical resistivity methods to examine the contributions of submarine groundwater discharges - Kun-kun Zhang; Xiu-jun Guo; Ning Li; Xi-qin Cui (Marine Georesources & Geotechnology, 2021)

Estimation of the vertically integrated leaf nitrogen content in maize using canopy hyperspectral red edge parameters - Pengfei Wen; Zujiao Shi; Ao Li; Fang Ning; Yuanhong Zhang; Rui Wang; Jun Li (Precision Agriculture, 2021)

Syntheses and anticancer activities of novel glucosylated (−)-epigallocatechin-3-gallate derivatives linked via triazole rings - Bo-Ya Shi; Ze-Hao Wang; Ning Zhang; Yin-Rong Xie; Xiu-Li Sun; Hao-Nan Yang; Yi-Long Wu; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Medicinal Chemistry Research, 2021)

ZnO nanorods/Fe3O4-graphene oxide/metal-organic framework nanocomposite: recyclable and robust photocatalyst for degradation of pharmaceutical pollutants - Li Chen; Jun Peng; Fangqi Wang; Donghao Liu; Wenrong Ma; Jinmeng Zhang; Wenqing Hu; Ning Li; Pierre Dramou; Hua He (Environmental Science and Pollution Research, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Scaling Orchestration in Physical Model Test of Oscillating Buoy Wave Energy Converter - Dongsheng Qiao; Guangning Zhi; Haizhi Liang; Dezhi Ning; Jun Yan; Binbin Li (Frontiers in Marine Science, 2021)
The physical model test interlinks the concept design and sea trial during the commercial utilization of wave energy converter. Aiming at the oscillating buoy wave energy converter, the energy conversion principle is firstly decomposed. Then, the model scale requirement of fluid motion and corresponding hydrodynamic similarity criterion considered in the physical model test are introduced. Finally, the solution of scaling orchestration problem is proposed considering the overall model scale in different energy conversion processes. The hydrodynamic similarity criterion is selected based on the working mechanism of the energy-capturing body only in contact with water, and the model scale requirements during the other stages of energy conversion structure are determined by the main mechanical factors. The first-stage energy conversion of device is recommended to meet the Froude similarity requirements, while the second-stage and third-stage energy conversions only need to meet the power similarity requirements. The power scale ratio in the three energy conversions is recommended to be consistent with the Froude similarity, and there are no requirements of geometric shape of second-stage and third-stage energy conversions to meet the similarity criteria.

Correction to: Glaciimonas soli sp. nov., a soil bacterium isolated from the forest of a high elevation mountain - Wei-Sheng Huang; Li-Ting Wang; Jun-Ning Sun; Jwo-Sheng Chen; Ssu-Po Huang; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2021)

Transient Responses Evaluation of FPSO with Different Failure Scenarios of Mooring Lines - Dongsheng Qiao; Binbin Li; Jun Yan; Yu Qin; Haizhi Liang; Dezhi Ning (Journal of Marine Science and Engineering, 2021)
During the long-term service condition, the mooring line of the deep-water floating platform may fail due to various reasons, such as overloading caused by an accidental condition or performance deterioration. Therefore, the safety performance under the transient responses process should be evaluated in advance, during the design phase. A series of time-domain numerical simulations for evaluating the performance changes of a Floating Production Storage and Offloading (FPSO) with different broken modes of mooring lines was carried out. The broken conditions include the single mooring line or two mooring lines failure under ipsilateral, opposite, and adjacent sides. The resulting transient and following steady-state responses of the vessel and the mooring line tensions were analyzed, and the corresponding influence mechanism was investigated. The accidental failure of a single or two mooring lines changes the watch circle of the vessel and the tension redistribution of the remaining mooring lines. The results indicated that the failure of mooring lines mainly influences the responses of sway, surge, and yaw, and the change rule is closely related to the stiffness and symmetry of the mooring system. The simulation results could give a profound understanding of the transient-effects influence process of mooring line failure, and the suggestions are given to account for the transient effects in the design of the mooring system.

IbERF71, with IbMYB340 and IbbHLH2, coregulates anthocyanin accumulation by binding to the IbANS1 promoter in purple-fleshed sweet potato (Ipomoea batatas L.) - Zhiyuan Ning; Kangdi Hu; Zhilin Zhou; Donglan Zhao; Jun Tang; Hong Wang; Lixia Li; Chen Ding; Xiaoyan Chen; Gaifang Yao; Hua Zhang (Plant Cell Reports, 2021)

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

NEURO-LEARN: a Solution for Collaborative Pattern Analysis of Neuroimaging Data - Bingye Lei; Fengchun Wu; Jing Zhou; Dongsheng Xiong; Kaixi Wang; Lingyin Kong; Pengfei Ke; Jun Chen; Yuping Ning; Xiaobo Li; Zhiming Xiang; Kai Wu (Neuroinformatics, 2021)

Spinal CCL2 Promotes Pain Sensitization by Rapid Enhancement of NMDA-Induced Currents Through the ERK-GluN2B Pathway in Mouse Lamina II Neurons - Hui Zhang; Sui-Bin Ma; Yong-Jing Gao; Jun-Ling Xing; Hang Xian; Zhen-Zhen Li; Shu-Ning Shen; Sheng-Xi Wu; Ceng Luo; Rou-Gang Xie (Neuroscience Bulletin, 2020)
Previous studies have shown that CCL2 (C–C motif chemokine ligand 2) induces chronic pain, but the exact mechanisms are still unknown. Here, we established models to explore the potential mechanisms. Behavioral experiments revealed that an antagonist of extracellular signal-regulated kinase (ERK) inhibited not only CCL2-induced inflammatory pain, but also pain responses induced by complete Freund’s adjuvant. We posed the question of the intracellular signaling cascade involved. Subsequent experiments showed that CCL2 up-regulated the expression of phosphorylated ERK (pERK) and N-methyl D-aspartate receptor [NMDAR] subtype 2B (GluN2B); meanwhile, antagonists of CCR2 and ERK effectively reversed these phenomena. Whole-cell patch-clamp recordings revealed that CCL2 enhanced the NMDAR-induced currents via activating the pERK pathway, which was blocked by antagonists of GluN2B and ERK. In summary, we demonstrate that CCL2 directly interacts with CCR2 to enhance NMDAR-induced currents, eventually leading to inflammatory pain mainly through the CCL2–CCR2–pERK–GluN2B pathway.

Deinococcus detaillensis sp. nov., isolated from humus soil in Antarctica - Kun Zhang; Jing Zhu; Shuai Li; Manik Prabhu Narsing Rao; Ning-Mei Li; Ang-Yang Guo; Zhao Jiang; Qi-Yong Tang; Yi Wan; Zhi-Dong Zhang; Wen-Jun Li (Archives of Microbiology, 2020)

Stabilization of soil aggregate and organic matter under the application of three organic resources and biochar-based compound fertilizer - Kun Chen; Jing Peng; Jun Li; Qian Yang; Xiumei Zhan; Ning Liu; Xiaori Han (Journal of Soils and Sediments, 2020)

A New Perspective on the Constant mi of the Hoek–Brown Failure Criterion and a New Model for Determining the Residual Strength of Rock - Mingming He; Zhiqiang Zhang; Jun Zheng; Fangfang Chen; Ning Li (Rock Mechanics and Rock Engineering, 2020)

Comparative analysis and natural evolution of squalene epoxidase in three Fritillaria species - Xu Lu; Lin-Ning Zhang; Jin-Fa Du; Xiao-Yan Zheng; Hui-Jun Li; Ping Li; Gui-Zhong Xin; Yan Jiang (Plant Molecular Biology, 2020)

Glaciimonas soli sp. nov., a soil bacterium isolated from the forest of a high elevation mountain - Wei-Sheng Huang; Li-Ting Wang; Jun-Ning Sun; Jwo-Sheng Chen; Ssu-Po Huang; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2020)

Control factors of DIC in the Y3 seamount waters of the Western Pacific Ocean - Jun Ma; Jinming Song; Xuegang Li; Huamao Yuan; Ning Li; Liqin Duan; Qidong Wang (Journal of Oceanology and Limnology, 2020)

Enhanced Antitumor Efficacy of Curcumin-Loaded PLGA Nanoparticles Coated with Unique Fungal Hydrophobin - Lu Sun; Hui Xu; Jing-hua Xu; Shao-ning Wang; Jun-wei Wang; Hong-feng Zhang; Wei-ru Jia; Lin-sen Li (AAPS PharmSciTech, 2020)

Integrated fate assessment of aromatic amines in aerobic sewage treatment plants - Lin Jun Zhou; Zhi Yi Rong; Wen Gu; De Ling Fan; Ji Ning Liu; Li Li Shi; Yan Hua Xu; Zhi Ying Liu (Environmental Monitoring and Assessment, 2020)
The fate and exposure of chemicals in sewage treatment plants (STPs) are major considerations in risk assessment and environmental regulation. The biodegradability and removal of seven aromatic amines were systematically evaluated using a three-tiered integrated method: a standard ready biodegradability test, an aerobic sewage treatment simulation method, and model prediction. In tier 1, the seven aromatic amines were not readily biodegraded after 28 days. In adapted aerobic active sludge, 4-isopropyl aniline, 2,4-diaminotoluene, and 4-nitroaniline among them exhibited the degradation half-life time less than 20 h, the other four aromatic amines exhibited persistent with degradation half-life of > 60 h. In tier 2 of the aerobic sewage treatment simulation testing, 2,4-diaminotoluene, 4-nitroaniline, and 4-isopropylaniline demonstrated moderately to high overall removal. Hydraulic retention time (HRT) affects the removal with the optimum HRT was determined to be 12 h to 24. 2,6-Dimethyl aniline, 2-chloro-4-nitroaniline, 2,6-diethylaniline, and 3,4-dichloroaniline were not removed during the test, indicting these four aromatic amines will enter surface water and hence pose a potential risk to aquatic ecology. Considering the lack of an STP model in China for regulation purposes, in tier 3, we developed a Chinese STP (aerobic) (abbreviated as C-STP(O)) model that reflects a universal scenario for China to predict the fate. The predicted degradation, volatilization, and absorption showed a close relationship to the physicochemical properties of the chemicals, and had same tendency with tier 2 simulation test. The prediction showed that biodegradation rather than absorption or volatilization was the main removal process of aromatic amines in aerobic STP. With the combination of modified kinetics test with C-STP (O) model, the chemical fate can be more accurately predicted than using only the readily biodegradation result.

Late Pleistocene environmental information on the Diexi paleo-dammed lake of the upper Minjiang River in the eastern margin of the Tibetan Plateau, China - Lan-sheng Wang; Xiao-qun Wang; Jun-hui Shen; Guan Yin; Jie Cui; Xiang-ning Xu; Zhi-long Zhang; Tao Wan; Li-wang Wen (Journal of Mountain Science, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Targeting gut microbiota with dietary components on cancer: Effects and potential mechanisms of action - Jun Tao; Sha Li; Ren-You Gan; Cai-Ning Zhao; Xiao Meng; Hua-Bin Li (Critical Reviews in Food Science and Nutrition, 2020)

The giant Zaozigou Au-Sb deposit in West Qinling, China: magmatic- or metamorphic-hydrothermal origin? - Kun-Feng Qiu; Hao-Cheng Yu; Jun Deng; Duncan McIntire; Zong-Yang Gou; Jian-Zhen Geng; Zhao-Shan Chang; Rui Zhu; Kang-Ning Li; Richard Goldfarb (Mineralium Deposita, 2020)

Arundo donax L. stem-derived biochar increases As and Sb toxicities from nonferrous metal mine tailings - Jihai Gu; Jun Yao; Gyozo Jordan; Beenish Roha; Ning Min; Hao Li; Chao Lu (Environmental Science and Pollution Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Development of a Gateway-compatible two-component expression vector system for plants - Ning Li; Deyi Yuan; Li-Jun Huang (Transgenic Research, 2019)

Two new labdane diterpenoids from aerial parts of Leonurus japonicus and their anti-inflammatory activity - Yu-Mei Hu; Wen-Jun Liu; Meng-Xuan Li; Hai-Bo Li; Tao Jiang; Ning-Bo Cheng; Wen-Zhe Huang; Zhen-Zhong Wang; Hua-Xu Zhu; Wei Xiao (Natural Product Research, 2019)

Ligustroflavone reduces necroptosis in rat brain after ischemic stroke through targeting RIPK1/RIPK3/MLKL pathway - Yi-Yue Zhang; Wei-Ning Liu; Yue-Qi Li; Xiao-Jie Zhang; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Differential Transcriptomic and Metabolomic Responses in the Liver of Nile Tilapia (Oreochromis niloticus) Exposed to Acute Ammonia - Zong Xian Zhu; Dan Li Jiang; Bi Jun Li; Hui Qin; Zi Ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Portable vertical pendulum tiltmeter development and application test - Jie-ning Xia; Qiang Lin; Li-Xia Geng; Zhen Li; Song Luo; Nong-Fa Li; Jian-Feng Yu; Jun Liu (Acta Geodaetica et Geophysica, 2019)

Identifying a Long QTL Cluster Across chrLG18 Associated with Salt Tolerance in Tilapia Using GWAS and QTL-seq - Dan Li Jiang; Xiao Hui Gu; Bi Jun Li; Zong Xian Zhu; Hui Qin; Zi ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Retinoic acid (RA) and bone morphogenetic protein 4 (BMP4) restore the germline competence of in vitro cultured chicken blastodermal cells - Xiaochuan Tang; Jun Shi; Xiaolian Qin; Ning Xiao; Rongyang Li; Hao Hu; Fengshuo Yang; Deshun Shi; Xiaoli Wang (In Vitro Cellular & Developmental Biology - Animal, 2019)

MnO2-loaded microorganism-derived carbon for U(VI) adsorption from aqueous solution - Wei Liao; Huilin Wang; Feize Li; Changsong Zhao; Jun Liu; Jiali Liao; Jijun Yang; Yuanyou Yang; Ning Liu (Environmental Science and Pollution Research, 2019)

Emerging role of circadian rhythm in bone remodeling - Qian-Yuan Wu; Jian Wang; Xiao Tong; Jie Chen; Bei Wang; Zong-Ning Miao; Xia Li; Jun-Xing Ye; Feng-Lai Yuan (Journal of Molecular Medicine, 2019)

Effects of long-term coastal reclamation on suitable habitat and wintering population size of the endangered Red-crowned Crane, Grus japonensis - Ning Li; Zheng Wang; Lu Xia; Feng Yan; Ling-qian Xu; Ya-jun Qiao; Xin-hai Li; Shu-qing An; Shu-bo Fang (Hydrobiologia, 2019)

Functions of PKS Genes in Lipid Synthesis of Schizochytrium sp. by Gene Disruption and Metabolomics Analysis - Zhipeng Li; Xi Chen; Jun Li; Tong Meng; Lingwei Wang; Zhen Chen; Yanyan Shi; Xueping Ling; Weiang Luo; Dafeng Liang; Yinghua Lu; Qingbiao Li; et al. (Marine Biotechnology, 2018)

Application of a Simple Quantitative Assessment of Atherosclerotic Lesions in Freshly Isolated Aortas from Rabbits - Li-Jun Zhao; Ying Xiao; Xia Meng; Ning Wang; Y. James Kang (Cardiovascular Toxicology, 2018)

Histamine Excites Striatal Dopamine D1 and D2 Receptor-Expressing Neurons via Postsynaptic H1 and H2 Receptors - Qian-Xing Zhuang; Han-Ting Xu; Xu-Juan Lu; Bin Li; Wing-Ho Yung; Jian-Jun Wang; Jing-Ning Zhu (Molecular Neurobiology, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

Novel alternatively spliced isoforms of MEF2A and their mRNA expression patterns in pigs - Xiao Hong Guo; Qi Zhang; Meng Li; Peng Fei Gao; Guo Qing Cao; Zhi Min Cheng; Ning Fang Zhang; Bao Yu Le; Jian Feng Liu; Xiao Jun Liu; Bu Gao Li (Journal of Genetics, 2018)

Atlas of the Striatum and Globus Pallidus in the Tree Shrew: Comparison with Rat and Mouse - Rong-Jun Ni; Zhao-Huan Huang; Yu-Mian Shu; Yu Wang; Tao Li; Jiang-Ning Zhou (Neuroscience Bulletin, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Seismic stability analysis of slopes with pre-existing slip surfaces - Li-jun Su; Chang-ning Sun; Fang-wei Yu; Sarfraz Ali (Journal of Mountain Science, 2018)

Transcriptome signatures of tomato leaf induced by Phytophthora infestans and functional identification of transcription factor SpWRKY3 - Jun Cui; Pinsan Xu; Jun Meng; Jingbin Li; Ning Jiang; Yushi Luan (Theoretical and Applied Genetics, 2018)

Safety, pharmacokinetics, and pharmacodynamics of S-(−)-pantoprazole sodium injections after single and multiple intravenous doses in healthy Chinese subjects - Hui-Wen Jiao; Lu-Ning Sun; Yue-Qi Li; Lei Yu; Hong-Wen Zhang; Mei-Feng Wang; Li-Yuan Yu; Zi-Qing-Yun Yuan; Li-Jun Xie; Juan Chen; Ling Meng; Xue-Hui Zhang; et al. (European Journal of Clinical Pharmacology, 2018)

Effective enhancement of resistance to Phytophthora infestans by overexpression of miR172a and b in Solanum lycopersicum - Yushi Luan; Jun Cui; Jie Li; Ning Jiang; Ping Liu; Jun Meng (Planta, 2018)

Mapping stripe rust resistance gene YrZH22 in Chinese wheat cultivar Zhoumai 22 by bulked segregant RNA-Seq (BSR-Seq) and comparative genomics analyses - Yong Wang; Jingzhong Xie; Huaizhi Zhang; Bingmin Guo; Shunzong Ning; Yongxing Chen; Ping Lu; Qiuhong Wu; Miaomiao Li; Deyun Zhang; Guanghao Guo; Yan Zhang; et al. (Theoretical and Applied Genetics, 2017)

Functionalized hydrothermal carbon derived from waste pomelo peel as solid-phase extractant for the removal of uranyl from aqueous solution - Feize Li; Yu Tang; Huilin Wang; Jijun Yang; Shoujian Li; Jun Liu; Hong Tu; Jiali Liao; Yuanyou Yang; Ning Liu (Environmental Science and Pollution Research, 2017)

Diabetic nephropathy: serum miR-9 confers a poor prognosis in and is associated with level changes of vascular endothelial growth factor and pigment epithelium-derived factor - Yanxin Xiao; Shuqin Guo; Yunliang Zhang; Zhiying Bian; Liyan Jia; Yanyun Hu; Jie Chen; Chao Yin; Ning Li; Dongxun Zhang; Xincui Zhao; Jun Wang (Biotechnology Letters, 2017)

Neuroprotection of dexmedetomidine against propofol-induced neuroapoptosis partly mediated by PI3K/Akt pathway in hippocampal neurons of fetal rat - Ning Zhang; Quan-ping Su; Wei-xia Zhang; Nian-jun Shi; Hao Zhang; Ling-ping Wang; Zhong-kai Liu; Ke-zhong Li (Journal of Zhejiang University-SCIENCE B, 2017)

Light use efficiency of a warm-temperate mixed plantation in north China - Xiaojuan Tong; Jinsong Zhang; Ping Meng; Jun Li; Ning Zheng (International Journal of Biometeorology, 2017)

Orexin Directly Enhances the Excitability of Globus Pallidus Internus Neurons in Rat by Co-activating OX1 and OX2 Receptors - He-Ren Gao; Qian-Xing Zhuang; Yong-Xiao Zhang; Zhang-Peng Chen; Bin Li; Xiao-Yang Zhang; Yi-Ting Zhong; Jian-Jun Wang; Jing-Ning Zhu (Neuroscience Bulletin, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Elements in Fine Particulate Matter (PM $$_{2.5}$$ 2.5 ) from Indoor Air During Household Stoves Coal Combustion at Xuanwei, China - K. H. Lui; C. S. Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Jinwen Li; Jun-Ji Cao; S. C. Lee; K. F. Ho (Aerosol Science and Engineering, 2017)

Medial cerebellar nucleus projects to feeding-related neurons in the ventromedial hypothalamic nucleus in rats - Bin Li; Qian-Xing Zhuang; He-Ren Gao; Jian-Jun Wang; Jing-Ning Zhu (Brain Structure and Function, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

GWAS analysis of QTL for enteric septicemia of catfish and their involved genes suggest evolutionary conservation of a molecular mechanism of disease resistance - Tao Zhou; Shikai Liu; Xin Geng; Yulin Jin; Chen Jiang; Lisui Bao; Jun Yao; Yu Zhang; Jiaren Zhang; Luyang Sun; Xiaozhu Wang; Ning Li; et al. (Molecular Genetics and Genomics, 2017)

Multiple across-strain and within-strain QTLs suggest highly complex genetic architecture for hypoxia tolerance in channel catfish - Xiaozhu Wang; Shikai Liu; Chen Jiang; Xin Geng; Tao Zhou; Ning Li; Lisui Bao; Yun Li; Jun Yao; Yujia Yang; Xiaoxiao Zhong; Yulin Jin; et al. (Molecular Genetics and Genomics, 2017)

Environmental controls of evapotranspiration in a mixed plantation in North China - Xiaojuan Tong; Jinsong Zhang; Ping Meng; Jun Li; Ning Zheng (International Journal of Biometeorology, 2017)

Heavy metal contamination status and source apportionment in sediments of Songhua River Harbin region, Northeast China - Ning Li; Yu Tian; Jun Zhang; Wei Zuo; Wei Zhan; Jian Zhang (Environmental Science and Pollution Research, 2017)

Distribution and risk assessment of heavy metals in sewage sludge after ozonation - Jian Zhang; Yu Tian; Jun Zhang; Ning Li; Lingchao Kong; Ming Yu; Wei Zuo (Environmental Science and Pollution Research, 2017)

Attraction of Coffee Bean Weevil, Araecerus fasciculatus, to Volatiles from the Industrial Yeast Kluyveromyces lactis - Shuai Yang; Xiang-Dong Mei; Xiao-Fang Zhang; Yao-Fa Li; Dongmei She; Tao Zhang; Jun Ning (Journal of Chemical Ecology, 2017)

New Labdane diterpenes from Hedychium yunnanense with cytotoxicity and inhibitory effects on nitric oxide production - Yu-Peng Li; Si-Meng Zhao; Jun-Ju Xu; Guang-Zhi Zeng; Yan Li; Ning-Hua Tan; Ye Yang (Natural Product Research, 2016)

Geographic distance and amorphous iron affect the abundance and distribution of Geobacteraceae in paddy soils in China - Hai-Yan Yuan; Long-Jun Ding; Ning Wang; Song-Can Chen; Ye Deng; Xiao-Ming Li; Yong-Guan Zhu (Journal of Soils and Sediments, 2016)

Characteristics of uranium biosorption from aqueous solutions on fungus Pleurotus ostreatus - Changsong Zhao; Jun Liu; Hong Tu; Feize Li; Xiyang Li; Jijun Yang; Jiali Liao; Yuanyou Yang; Ning Liu; Qun Sun (Environmental Science and Pollution Research, 2016)

Occurrence and fate of PBDEs and novel brominated flame retardants in a wastewater treatment plant in Harbin, China - Bo Li; Shao-Jing Sun; Chun-Yan Huo; Wen-Long Li; Ning-Zheng Zhu; Hong Qi; Ling-Jun Kong; Yi-Fan Li; Wan-Li Ma (Environmental Science and Pollution Research, 2016)

BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

TNFα-induced M-MDSCs promote transplant immune tolerance via nitric oxide - Fan Yang; Yang Li; Tingting Wu; Ning Na; Yang Zhao; Weiguo Li; Chenlu Han; Lianfeng Zhang; Jun Lu; Yong Zhao (Journal of Molecular Medicine, 2016)

Interaction between STAT3 gene polymorphisms and smoking on Crohn’s disease susceptibility: a case–control study in a Chinese Han population - Jun-hong Li; Ning Wu; Hong-mei Yang; Hong-bing Tang; Dong-ping Bao; Jun-min Ji (Inflammation Research, 2016)

Characterization of the life cycle of the tick Haemaphysalis tibetensis under field conditions in Qinghai-Tibet plateau - Ming Liu; Tuo Li; Zhi-Jun Yu; Xiao-He Gao; Chun-Wei Zuo; Rong-Rong Wang; Ning-Xin Li; Hui Wang; Jing-Ze Liu (Experimental and Applied Acarology, 2016)

Selective Modulation of Histaminergic Inputs on Projection Neurons of Cerebellum Rapidly Promotes Motor Coordination via HCN Channels - Jun Zhang; Qian-Xing Zhuang; Bin Li; Guan-Yi Wu; Wing-Ho Yung; Jing-Ning Zhu; Jian-Jun Wang (Molecular Neurobiology, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

ALDH2*2 Allele is a Negative Risk Factor for Cerebral Infarction in Chinese Women - Qiao-Yan Li; Ning-Min Zhao; Jian-Jun Ma; Hong-Fei Duan; Yong-Cheng Ma; Wei Zhang; Hong-Wei Zhao; Yu-Hua Qin (Biochemical Genetics, 2015)

Isolation of differentially expressed sex genes in garden asparagus using suppression subtractive hybridization - Chuan-liang Deng; Ning-na Wang; Shu-fen Li; Tian-yu Dong; Xin-peng Zhao; Shao-jing Wang; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2015)

Responses to simulated nitrogen deposition in invasive and native or non-invasive clonal plants in China - Hong-Li Li; Lei Ning; Peter Alpert; Jun-Min Li; Fei-Hai Yu (Plant Ecology, 2014)

Cerebral hemodynamic characteristics of acute mountain sickness upon acute high-altitude exposure at 3,700 m in young Chinese men - Shi-Zhu Bian; Jun Jin; Qian-Ning Li; Jun Qin; Ji-Hang Zhang; Shi-Yong Yu; Jian-Fei Chen; Cai-Fa Tang; Lan Huang (European Journal of Applied Physiology, 2014)

5-HT2A receptor-mediated excitation on cerebellar fastigial nucleus neurons and promotion of motor behaviors in rats - Chang-Zheng Zhang; Qian-Xing Zhuang; Ye-Cheng He; Guang-Ying Li; Jing-Ning Zhu; Jian-Jun Wang (Pflügers Archiv - European Journal of Physiology, 2014)

Notch inhibition promotes fetal liver stem/progenitor cells differentiation into hepatocytes via the inhibition of HNF-1β - Tao Wang; Tao Chen; Hong-yin Liang; Hong-tao Yan; Ning Lin; Li-ye Liu; Hao Luo; Zhu Huang; Nan-lin Li; Wei-hui Liu; Li-jun Tang (Cell and Tissue Research, 2014)

Extraction of bridges over water from high-resolution optical remote-sensing images based on mathematical morphology - Chao Chen; Qiming Qin; Ning Zhang; Jun Li; Li Chen; Jun Wang; Xuebin Qin; Xiucheng Yang (International Journal of Remote Sensing, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Protection of MES23.5 dopaminergic cells by obestatin is mediated by proliferative rather than anti-apoptotic action - Xiao-Li Shen; Feng-Ju Jia; Ning Song; Jun-Xia Xie; Hong Jiang (Neuroscience Bulletin, 2014)

Chromium level and intake from Chinese made tea - Wei-hao Li; Hai-ping Zhou; Ning Li; Sai-di Wang; Xiao-juan Liu; Zeng-jun Jin; Yan-zhen Bu; Zhi-xue Liu (Food Additives & Contaminants Part B-Surveillance, 2013)

Consistency of the Key Genotypes of Orientia tsutsugamushi in Scrub Typhus Patients, Rodents, and Chiggers from a New Endemic Focus of Northern China - Yun-Xi Liu; Na Jia; Yu-Bin Xing; Ji-Jiang Suo; Ming-Mei Du; Ning Jia; Yan Gao; Li-Jun Xie; Bo-Wei Liu; Shi-Wang Ren (Cell Biochemistry and Biophysics, 2013)

6-Hydroxydopamine promotes iron traffic in primary cultured astrocytes - Hao-Yun Zhang; Nai-Dong Wang; Ning Song; Hua-Min Xu; Li-Min Shi; Hong Jiang; Jun-Xia Xie (BioMetals, 2013)

Partial AZFc duplications not deletions are associated with male infertility in the Yi population of Yunnan Province, China - Jun-jie Ye; Li Ma; Li-juan Yang; Jin-huan Wang; Yue-li Wang; Hai Guo; Ning Gong; Wen-hui Nie; Shu-hua Zhao (Journal of Zhejiang University-SCIENCE B, 2013)

DNA methylation alterations of upland cotton (Gossypium hirsutum) in response to cold stress - Hong Hong Fan; Jun Wei; Ting Chun Li; Zheng Peng Li; Ning Guo; Yong Ping Cai; Yi Lin (Acta Physiologiae Plantarum, 2013)

Chemistry, bioactivity and quality control of Dendrobium, a commonly used tonic herb in traditional Chinese medicine - Jun Xu; Quan-Bin Han; Song-Lin Li; Xiao-Jia Chen; Xiao-Ning Wang; Zhong-Zhen Zhao; Hu-Biao Chen (Phytochemistry Reviews, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Establishment of SYBR green-based qPCR assay for rapid evaluation and quantification for anti-Hantaan virus compounds in vitro and in suckling mice - Fei Wei; Jin-lin Li; Jia-xin Ling; Liang-Jun Chen; Ning Li; Yuan-Yuan Liu; Fan Luo; Hai-Rong Xiong; Wei Hou; Zhan-Qiu Yang (Virus Genes, 2013)

A meta-analysis of the relationship between glutathione S-transferases gene polymorphism and hepatocellular carcinoma in Asian population - Jie Chen; Liang Ma; Ning-Fu Peng; Shi-Jun Wang; Le-Qun Li (Molecular Biology Reports, 2012)

Comparative analysis of water stress-responsive transcriptomes in drought-susceptible and -tolerant wheat (Triticum aestivum L.) - Yong Chun Li; Fan Rong Meng; Chun Yan Zhang; Ning Zhang; Ming Shan Sun; Jiang Ping Ren; Hong Bin Niu; Xiang Wang; Jun Yin (Journal of Plant Biology, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Polymorphisms in chicken extracellular fatty acid binding protein gene - Zhi-yuan Zhao; Li Zhang; Bing-wang Du; Ning-xian Cao; Xin-sheng Jiang; Wen-xia Tian; Shu-jun Li; Wei-wei Wu; Chang-hui Ye (Molecular Biology Reports, 2012)

Electrophysiologic Characteristics of the Crista Terminalis and Implications on Atrial Tachycardia in Rabbits - Jin Li-jun; Liu Xue-yin; Huang Cong-xin; Yang Bo; Yang Sha-ning; Wu Gang; Xie Qiang; Liu Huang-jun (Cell Biochemistry and Biophysics, 2012)

Identification of a suitable endogenous control gene in porcine blastocysts for use in quantitative PCR analysis of microRNAs - Jun Li; HengXi Wei; Yan Li; QiuYan Li; Ning Li (Science China Life Sciences, 2012)

The effect of down regulation of calcineurin Aα by lentiviral vector-mediated RNAi on the biological behavior of small-cell lung cancer and its bone metastasis - Ning-Qiang Ma; Li-Li Liu; Jie Min; Jun-Wei Wang; Wei-Feng Jiang; Yan Liu; Yan-Guo Feng; Hai-Chuan Su; Ying-Ming Feng; He-Long Zhang (Clinical & Experimental Metastasis, 2011)

A high-frequency cyclic secondary somatic embryogenesis system for Cyclamen persicum Mill - Cui Rong You; Ting Jun Fan; Xue Qin Gong; Fu Hua Bian; Li Kun Liang; Fu Ning Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

RNASEL −1385G/A polymorphism and cancer risk: a meta-analysis based on 21 case–control studies - Li-Feng Zhang; Yuan-Yuan Mi; Chao Qin; Yong Wang; Qiang Cao; Jun-Feng Wei; Yao-Jun Zhou; Ning-Han Feng; Wei Zhang (Molecular Biology Reports, 2011)

Insulin-like growth factor-1 receptor activation prevents hydrogen peroxide-induced oxidative stress, mitochondrial dysfunction and apoptosis - Chang-Ning Hao; Yong-Jian Geng; Fan Li; Tong Yang; Ding-Feng Su; Jun-Li Duan; Yangxin Li (Apoptosis, 2011)

Tissue-specific and expression of porcine growth hormone gene in BAC transgenic mice - Jia Tong; Simon G. Lillico; Ming Jun Bi; Tong Qing; Xiao Fang Liu; YuanYuan Wang; Min Zheng; Meili Wang; Yun Ping Dai; C. Bruce A. Whitelaw; Ning Li (Transgenic Research, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Improvement of spinosad production by overexpression of gtt and gdh controlled by promoter PermE* in Saccharopolyspora spinosa SIPI-A2090 - Hai-Xue Pan; Ji-An Li; Ning-Jun He; Ji-Ye Chen; Yu-Meng Zhou; Lei Shao; Dai-Jie Chen (Biotechnology Letters, 2011)

Cloning and characterization of a novel CONSTANS-like gene from Phalaenopsis hybrida - Jian-Xia Zhang; Kun-Lin Wu; Li-Ning Tian; Song-Jun Zeng; Jun Duan (Acta Physiologiae Plantarum, 2011)

Recombinant adenovirus-mediated expression of GHS-R1a in HEK 293 cells - Li Liu; Hua-Min Xu; Hong Jiang; Jun Wang; Ning Song; Jun-Xia Xie (Neuroscience Bulletin, 2010)

Dose- and time-dependent α-synuclein aggregation induced by ferric iron in SK-N-SH cells - Wen-Jing Li; Hong Jiang; Ning Song; Jun-Xia Xie (Neuroscience Bulletin, 2010)

Neurochip based on light-addressable potentiometric sensor with wavelet transform de-noising - Qing-jun Liu; Wei-wei Ye; Hui Yu; Ning Hu; Li-ping Du; Ping Wang (Journal of Zhejiang University-SCIENCE B, 2010)

Epidemiological study of human calicivirus infection in children with gastroenteritis in Lanzhou from 2001 to 2007 - Wei-xia Cheng; Xin-hua Ye; Xue-mei Yang; Yu-ning Li; Miao Jin; Yu Jin; Zhao-jun Duan (Archives of Virology, 2010)

Magnetic cell sorting and flow cytometry sorting methods for the isolation and function analysis of mouse CD4+ CD25+ Treg cells - Hang Yan; Chen-guang Ding; Pu-xun Tian; Guan-qun Ge; Zhan-kui Jin; Li-ning Jia; Xiao-ming Ding; Xiao-ming Pan; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2009)

Rosmarinic Acid Inhibits 6-OHDA-induced Neurotoxicity by Anti-oxidation in MES23.5 Cells - Pei Ren; Hong Jiang; Ronggui Li; Jun Wang; Ning Song; Hua-Min Xu; Jun-Xia Xie (Journal of Molecular Neuroscience, 2009)

Epigallocatechin-3-gallate affects the growth of LNCaP cells via membrane fluidity and distribution of cellular zinc - Jun-guo Yang; Hai-ning Yu; Shi-li Sun; Lan-cui Zhang; Guo-qing He; Undurti N. Das; Hui Ruan; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2009)

Minocycline attenuates cognitive impairment and restrains oxidative stress in the hippocampus of rats with chronic cerebral hypoperfusion - Zhi-You Cai; Yong Yan; Shan-Quan Sun; Jun Zhang; Liang-Guo HUANG; Ning Yan; Fang Wu; Jie-Ying Li (Neuroscience Bulletin, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Molecular Cloning and Single Nucleotide Polymorphism Detection of Buffalo DGAT1 Gene - Jing Yuan; Jun Zhou; Xuemei Deng; Xiaoxiang Hu; Ning Li (Biochemical Genetics, 2007)

Variants of Green Fluorescent Protein GFPxm - Wen-Xin Luo; Tong Cheng; Bao-Quan Guan; Shao-Wei Li; Ji Miao; Jun Zhang; Ning-Shao Xia (Marine Biotechnology, 2006)

Variants of Green Fluorescent Protein GFPxm - Wen-Xin Luo; Tong Cheng; Bao-Quan Guan; Shao-Wei Li; Ji Miao; Jun Zhang; Ning-Shao Xia (Marine Biotechnology, 2006)

A Pilot Study of Transcription Unit Analysis in Rice Using Oligonucleotide Tiling-path Microarray - Viktor Stolc; Lei Li; Xiangfeng Wang; Xueyong Li; Ning Su; Waraporn Tongprasit; Bin Han; Yongbiao Xue; Jiayang Li; Michael Snyder; Mark Gerstein; Jun Wang; et al. (Plant Molecular Biology, 2005)

Human embryonic germ cells isolation from early stages of post-implantation embryos - ShanRong Liu; HouQi Liu; YuQiong Pan; ShuPing Tang; Jun Xiong; Ning Hui; ShuLing Wang; ZhongTian Qi; LingSong Li (Cell and Tissue Research, 2004)

Bioluminescence of Aequorea macrodactyla, a Common Jellyfish Species in the East China Sea - Ning-Shao Xia; Wen-Xin Luo; Jun Zhang; Xiao-Yan Xie; Hai-Jie Yang; Shao-Wei Li; Ming Chen; Mun-Hon Ng (Marine Biotechnology, 2002)